Aerosol modulation of precipitation systems migrating from mountains to plains in Northern China during early autumn - Yu Zheng; Yucong Miao; Shuhua Liu; Huizheng Che (Atmospheric Research, 2027)

Dopamine triggers TOR signaling cascade to drive biomass and astaxanthin hyperaccumulation in Haematococcus lacustris under coordinated salinity and gradient light stress - Shiyu Lin; Qingwei Wang; Raoqiong Che; Qingqing Li; Chunli Yu; Min Yang; Lifang Li; Penghua Gao; Ying Qi; Feiyan Huang; Xiang Wang; Yongteng Zhao; et al. (Bioresource Technology, 2026)

Excavatolide E triggers oxidative stress-associated apoptosis and DNA damage to inhibit bladder cancer cell proliferation - Che-Wei Yang; Chia-Hung Yen; Tsu-Ming Chien; Szu-Yin Yu; Fang-Rong Chang; Jyh-Horng Sheu; Hsueh-Wei Chang (Molecular Biology Reports, 2026)

Tidal air exposure thresholds in seagrass survival: photodamage-antioxidant imbalance and anthocyanin accumulation associated with Enhalus acoroides zonation limits - Hu Li; Shuju Guo; Mengjie Zhang; Tie Zhang; Litao Zhang; Xingkai Che; Wenjie Yu; Jianguo Liu (Marine Pollution Bulletin, 2026)

Devonian Jinshuikou pegmatites at the northern margin of the Tibetan Plateau: UPb and SmNd constraints on their genetic relationship with regional granitoids - Si-Qi Liu; Shao-Yong Jiang; Mostafa Fayek; Hui-Min Su; Yu-Ying Che; Wei Wang; Qinglin Xia (Lithos, 2026)

Electron-percolation-driven electric-field harmonization reprograms Zn nucleation for ultrastable Zn metal anodes - Jia-Sheng Lin; Daniel Chang; Che-Ning Yeh; Yi-Chun Yang; Hsing-Yu Tuan (Chemical Engineering Journal, 2026)

Agricultural management intensity drives niche partitioning of ammonia oxidizers at three contrasting soil sites - Yu Zeng; Che Tan; Chang Yin; Xiaozhong Wang; Hongsheng Gao; Hua Peng; Yongchao Liang (Applied Soil Ecology, 2026)

Arginine and putrescine ameliorate heat stress-induced testicular inflammation and apoptosis via inhibiting endoplasmic reticulum stress in mice - Kun Wu; Chenglong Yu; Guangmang Liu; Yong Zhuo; Bin Feng; Lianqiang Che; Shengyu Xu; Lun Hua; Jian Li; Zhengfeng Fang; De Wu; Yan Lin (Theriogenology, 2026)

Mine water as a multidimensional resource: A critical process engineering review of water-energy‑carbon nexus technologies, maturity assessment and scale-up challenges - Che Lulu; Li Bo; Yang Ya; Yang Yu; Luo Ye; Li Tao (Journal of Water Process Engineering, 2026)

Engineering Co-N4 active sites in heptazine-porphyrin organic polymer to boost non-radical singlet oxygen generation in peroxymonosulfate activation - Xiang Li; Yu Tian; Yalong Xu; Bo Liu; Shi Zhou; Wei Jiang; Chunbo Liu; Guangbo Che (Journal of Environmental Chemical Engineering, 2026)

Deciphering the long-term performance and underlying mechanisms of an engineering-scale anaerobic-anoxic-oxic-anaerobic-vibrating MBR process - Shujuan Che; Weichen Lin; Haojie Ding; Congcong Zhang; Xiangyu Li; Kaichang Yu; Huanhuan Guan; Jie Shi; Yun Yang; Xia Huang (ENGINEERING Environment, 2026)

Metagenomics indicates new taxa in Candidatus Saccharimonadia and proposal of Parviradicicola hetaonensis gen. nov. sp. nov. and Parviputeicola dengkouensis gen. nov. sp. nov. following the rules of the SeqCode - Yanxing Wang; Lijia Ye; Chunling Cao; Gen Che; Chengzhi Zhang; Qiuqin Wei; Yu Hong; Kai Jiang (Systematic and Applied Microbiology, 2026)

Conserved crop root economics space drives niche partitioning of ammonia oxidizers - Yu Zeng; Che Tan; Zhihui Wen; Jianbo Shen; Chang Yin; Yongchao Liang (Soil Biology and Biochemistry, 2026)

Chlorpyrifos exposure induces inflammatory and immune dysregulation: An integrative in silico and in vitro analysis - Chen-Yu Chiang; Shih-Pin Chen; Ci-Wen Luo; Chun-Hung Su; Shiuan-Shinn Lee; Wen-Ying Chen; Chun-Jung Chen; Ching-Chi Tseng; Pin-Tzu Chen; Yin-Che Lu; Yu-Hsiang Kuan (Pesticide Biochemistry and Physiology, 2026)

Risk-controlled resource recovery from hazardous phenol wastewater: Co-production of p-benzoquinone and hydrogen with a noble-metal-free WO3-Ni(OH)x/NF bifunctional electrode - Yuhan Liu; Yu Sheng; Zihao Fan; Tongyu Che; Jiahui Yang; Anran Deng; Zhongfei Ren; Fang Liu (Journal of Hazardous Materials, 2026)

Aedes aegypti calreticulin promotes dengue virus replication and transmission by glycan-dependent binding to the prM protein - Shih-Che Weng; Yu-Chieh Hsu; Po-Nien Tsao; Shin-Hong Shiao (Insect Biochemistry and Molecular Biology, 2026)

Flash-Joule carbon-based hierarchical evaporator for water recovery and synergistic heavy-metal sequestration from E-waste leachates - Chenxu Zhong; Chujun Luan; Jianlin Yu; Lei Che; Guanyi Chen; Fawei Lin (Chemical Engineering Journal, 2026)

Identify conservation gaps and devise sustainable use strategies using orchid flora as a proxy - Hong Liu; Emily Jefferson; Shao-Ting Lin; Che-Yu Lin; Chun-Ming Chen; Dominic Mellone; Wen-Chieh Tsai (Biodiversity and Conservation, 2026)

Heterochromatin protein 1 (HP1) dysfunction drives male-biased sex ratio in Trichogramma dendrolimi (Hymenoptera: Trichogrammatidae) via paternal genome elimination during mitosis - Zhi-chao Jia; Hong-yu Liang; Yu-han Xu; Ning He; Wu-nan Che; Yue Shi; Hui Dong (Chromosome Research, 2026)

Activation-optimized anti-CD3 valency control enables combinatorial discovery of multi-specific nanoantibodies for solid tumor immunotherapy - Long Zhu; Ya-Jing Ma; Jian-Kang Kang; Xiu-Hai Che; Dong-Kun Zhao; Yin-Yi Cai; Yao-Ru Yu; Song Shen; Jun Wang (Science Bulletin, 2026)

A circular “capture-and-upcycle” strategy for micro/nano-plastic remediation: From aquatic pollutants to fire-safe composites - Zhuo Huang; Jiawei Ying; Long Liu; Jiantao Zheng; Youming Yu; Wenhui Bao; Wenbo Che (Journal of Hazardous Materials, 2026)

Caffeinated chewing gum improves military performances in special forces soldiers - Yi-Jie Shiu; Che-Hsiu Chen; Hung-Yu Lin; Chia-Cheng Yang; Chi-Wen Yen; Han-Yuan Chang; Hsuan-Ta Chen; Chih-Hui Chiu (European Journal of Applied Physiology, 2026)

Continuous Diurnal–Nocturnal Observation of Atmospheric Aerosols: Mechanisms, Challenges, and the Prospects of AI Empowerment - Huizheng Che; Yu Zheng; Lei Li; Ke Gui; Hengheng Zhao; Junli Jin; Xiaochun Zhang; Xiang’ao Xia; Yupeng Wang; Zhiwei Xia; Yucong Miao; Yaqiang Wang; et al. (Journal of Meteorological Research, 2026)

Thermal dynamics of an intermittent subtropical stream controlled by surface water-groundwater interactions: evidence from distributed temperature sensing and heat-budget modeling - Yen-Wei Pan; Yu-Cheng Chen; Tsung-Yu Lee; Yung-Chia Chiu; Shao-Yu Hsu; Che-Ming Chen (Environmental Monitoring and Assessment, 2026)

Spatiotemporal evolution and ecological risk assessment of heavy metals in agricultural black soils of Northeast China - Tianhao Che; Boling Deng; Naiwen Hu; Meixuan Wu; Hongwen Yu; Jing Yue; Quanying Wang (Environmental Research, 2026)

Assessment of quasi-global surface ozone simulations with WRF-chem using multi-dataset evaluation - Lingxia Wu; Lei Li; Lei Zhang; Yadong Lei; Shuhui Liu; Haoling Zhang; Ke Gui; Yu Zheng; Huizheng Che (Environmental Pollution, 2026)

Impacts of freeze-thaw cycles on nutrient release in agricultural soils: An integrated analysis using meta-analysis, machine learning, and field validation - Tianhao Che; Xiutao Yang; Hongwen Yu; Guankai Qiu; Quanying Wang; Yunjiang Liang (Journal of Soils and Sediments, 2026)

Efficacy of NEPA for prevention of chemotherapy induced nausea and vomiting in head and neck cancer patients receiving cisplatin-based chemotherapy - Tzer-Zen Hwang; Chih-Chun Wang; Chuan-Chien Yang; Ching-Feng Lien; Chien-Chung Wang; Yu-Chen Shih; Shyh-An Yeh; Tai-Heng Yeh; Meng-Che Hsieh (European Journal of Clinical Pharmacology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

An oil shale ash-based Fe3O4@NaY magnetic zeolite with rapid and high removal efficiency for crystal violet - Yu Duan; Qitao Liu; Qian Wang; Yuanjun Che; Hongchen Liu; Fei Li (Journal of Environmental Chemical Engineering, 2026)

Fe-doped BiOBr nanosheets vertically grown on TiO2 nanotube arrays for photoelectrocatalytic treatment of reclaimed water - Gui Yang; Yu Yan; Xing Wan; Huan He; Jingxian Mei; Meina Zhu; Huachao Che; Junhui Zhang; Juhong Zhan; Xiaoyong Wu; Bin Huang; Xuejun Pan (Journal of Environmental Sciences, 2026)

Corrigendum to ‘Coupled effects of glyphosate on soil carbon cycling regulated by dose, time, and environment: A global meta-analysis’ [Environ. Res. 299 (2026), Article 124281] - Yu Chu; Tianhao Che; Xinran Gao; Panxing He; Yang Li; Yu Ma (Environmental Research, 2026)

Coupled effects of glyphosate on soil carbon cycling regulated by dose, time, and environment: A global meta-analysis - Yu Chu; Tianhao Che; Xinran Gao; Panxing He; Yang Li; Yu Ma (Environmental Research, 2026)

Assessing earthquake-induced displacements of large-scale landslide by in-situ monitoring and discrete element analysis - Meng-Chia Weng; Wei-An Chao; Che-Ming Yang; Tee-Ann Teo; Kuo-Wei Li; Yu-Ting Hsiao (Engineering Geology, 2026)

Repurposing tumor-derived extracellular vesicles with an adhesive carboxymethyl chitosan-based hydrogel for spinal cord injury repair - Kuan-Lin Wang; Yu-Che Hsiao; Wen-Yu Pan; Chun-Jung Lin; Chieh-Cheng Huang; Yu-Jung Lin (Carbohydrate Polymers, 2026)

Nanocellulose-based ion-exchange membranes for salinity-gradient osmotic energy conversion - Xinlei Yu; Liming Zhang; Honglin Che; Mengyu Liu; Jinghuan Chen; Chao Tian; Jingwei Chen; Minghua Huang; Jingyi Wu; Huanlei Wang; Feng Xu; Weiqian Tian (Carbohydrate Polymers, 2026)

Global radiative forcing assessment of brown carbon versus black carbon: Source-specific constraints from compiled observations - Shuhui Liu; Lei Li; Xindan Zhang; Yadong Lei; Haoling Zhang; Yu Zheng; Ke Gui; Hengheng Zhao; Jingrui Ma; Zhili Wang; Huizheng Che; Xiaoye Zhang (Atmospheric Environment, 2026)

Life cycle environmental impact of customer premises equipment: insights from a Wi-Fi router case study - Hsin-Tien Lin; Kuo-Che Weng; En-Yu Yeh; Chun-Wei Wang; Han-Chang Pan (The International Journal of Life Cycle Assessment, 2026)

Regulatory patterns and driving factors of soil aggregates on the environmental behavior of heavy metals: A global study based on meta-analysis and machine learning - Yu-Xuan Song; Yuhan Meng; Bingxuan Zhao; Tian-Hao Che; Zining Li; Zuozhou Yu; Xinyang Zhen; Yining Li; Chengyong Li; Quan-Ying Wang; Jing-Ya Zhou (Environmental Geochemistry and Health, 2026)

Doxorubicin-Induced Cardiotoxicity in Breast Cancer: Mechanistic Pathways, Pharmacogenomic Modifiers, and Translational Strategies - Chi-Tong Kuok; Hao-Wei Lee; Chen-Yu Huang; Yu-Che Cheng; Shih-Chang Lin; Jiun-Wen Guo (Cardiovascular Toxicology, 2026)

Luteolin-stabilized pickering emulsion for encapsulating Enterococcus hirae: preparation, characterization, and synergistic effects on hyperuricemia - Chengtao Han; Songhao Che; Hui-Min Li; Yan-Yu Chi; Jun-Yan Xiang; Qiuhong Xie; Hongyu Xiang (Food Research International, 2026)

Using ChatGPT to Solve Clinical Radiobiology Problems - Che-Wei Su; Kun-Yao Dai; Yu-Jen Chen; Yung-Shuo Kao (Journal of Cancer Education, 2026)

Surface-confinement strategy enabling ultrahigh filler loading in adsorptive membranes for selective TBBPA separation and antifouling performance - Chao Yu; Junjie Ni; Daoyue Xie; Yilin Wu; Huinan Che; Yanhui Ao (Water Research, 2026)

Deposition characterization and predictive modeling of phosphorus and heavy metals during sewage sludge incineration - Qianqian Guo; Taojie Duan; Yanjun Hu; Long Jiao; Lingqin Zhao; Fan Yu; Xu Wang; Lei Che; Frederik Ronsse (Journal of Environmental Management, 2026)

Valorization of fly ash into hydrophobic mesoporous SiO₂ as a highly efficient and durable antifoaming agent for wet flue gas desulfurization - Fei Wang; Xiaoyan Yan; Xiaoke Li; Jiangtao Meng; Yu Che; Jing Wang; Yuanyuan Zhang (Journal of Environmental Chemical Engineering, 2026)

Decipher fouling's microscale hydrodynamic conditions around hollow fiber vibrating membrane - Lingping Zhang; Dawei Yu; Shujuan Che; Yuansong Wei (Desalination, 2026)

Corrigendum to “AI-driven process-tolerant BioFET sensing model for precise biliary atresia diagnosis of infants with a single drop of blood” [Chem. Eng. J. (2026), volume 531, 1 March 2026, 173939] - Chia-Kai Lin; Chi-Ming Ku; Chia-Che Wu; Yi-Fang Wu; Huey-Ling Chen; Yueh-Ju Hou; Arnab Pal; Zong-Hong Lin; Chee-Seng Lee; Tzong-Rong Ger; Yu-Lin Wang (Chemical Engineering Journal, 2026)

The enhanced nitrous oxide emissions are driven by prokaryotic ammonia oxidizers and nirK-denitrifiers under various combinations of nitrogen and rice straw in a paddy soil - Chunyan Wu; Yinxiu Liu; Xu Tang; Tao Sun; Che Tan; Yu Zeng; Yan Li; Chang Yin; Yongchao Liang (Soil Ecology Letters, 2026)

Structure–reactivity relationships in UV/chlorine degradation, NDMA formation, and cytotoxicity of chlorpheniramine and doxylamine - Shih-Wen Peng; Pei-Jin Lin; Ya-Hong Lin; Che-Hsin Lee; Yu-Chun Tseng; Ming-Cyuan He; Wei-Hsiang Chen (Journal of Hazardous Materials, 2026)

Estimation of grassland carrying capacity based on forage quantity/nutritional quality and livestock/wild ungulates in Changtang Nature Reserve on the Qinghai-Tibetan Plateau - Yunling Che; Yiming Xu; Yunmeng Qin; Shikui Dong; Zidong Zhou; Dian Yu (Journal of Environmental Management, 2026)

The rupture process of the September 2022 Guanshan and Chishang Earthquakes: Joint inversion of seismological and geodetic data - Wei-Yu Zhang; Yu-Sheng Sun; Yopi Serhalawan; Po-Fei Chen; Ming-Che Hsieh; Wu-Lung Chang (Journal of Asian Earth Sciences, 2026)

A novel approach for utilizing UAV imaging and deep learning techniques for river channel measurement and flood simulation - Jen-Yu Han; Chun-Jia Huang; Yuan-Shun Chang; Yen-Cheng Lin; Hao-Che Ho (Geomorphology, 2026)

Noise-resistant automatic seismic framework for monitoring rockslide slope - Chung-Ray Chu; Chiao-Yin Lu; Guan-Wei Lin; En-Jui Lee; Che-Hsin Liu; Chih-Hsin Chang; Hsiao-Yu Huang (Engineering Geology, 2026)

AI-driven process-tolerant BioFET sensing model for precise biliary atresia diagnosis of infants with a single drop of blood - Chia-Kai Lin; Chi-Ming Ku; Chia-Che Wu; Yi-Fang Wu; Heuy-Ling Chen; Yueh-Ju Hou; Arnab Pal; Zong-Hong Lin; Chee-Seng Lee; Tzong-Rong Ger; Yu-Lin Wang (Chemical Engineering Journal, 2026)

Mechanisms of water-state transformations in low-temperature thermal dewatering of sludge: Synergistic control via extracellular protein α-helix conformation and water–solid interfacial affinity - Nan Tian; Yu Hua; Fei Wang; Kai Zhang; Yuanyuan Zhang; Jing Wang; Yu Che; Jiangtao Meng; Fangqin Cheng (Bioresource Technology, 2026)

Low-temperature photothermal catalytic reforming: a promising approach for deep removal of biomass tar towards green fuels synthesis - Tianxiao Yu; Beibei Yan; Jian Li; Yuechi Che; Xiaopeng Jia; Guanyi Chen (Biomass and Bioenergy, 2026)

Ball-milling pretreatment-driven low-temperature waste cotton fibers-based hard carbon anodes for sodium-ion batteries - Yingying Zhou; Tiantao Huang; Zixin Lv; Che Wang; Junjun Peng; Aiping Jin; Jun Xiong; Linghui Yu; Ming Li; Zhongchen Ma; Jinchao Wei; Qing Chen (Biomass and Bioenergy, 2026)

Planococcus Daihaiensis sp. nov. Isolated from the Lake Water in Daihai - Gen Che; Kai Jiang; Chunling Cao; Lijia Ye; Yanxing Wang; Yu Hong (Current Microbiology, 2026)

LSTM-CNN-CBAM-based prediction of NOx emissions with zonal control strategies for flexible peak-load NOx reduction in CFB coal-fired units - Jing Wang; Xinwen Liao; Yu Che; Pengcheng Wang; Yuanyuan Zhang; Fei Wang; Frédéric Marias; Haojie Rong (Journal of Cleaner Production, 2026)

Phosphorus release and microbial community alterations in submerged areas of Qinghai Lake - Daye He; Yiming Zhao; Feifei Che; Shuhang Wang; Xia Jiang; Fuwen Deng; Xufeng Mao; Zheng Yu; Yunyan Guo (Gondwana Research, 2026)

Phthalate ester pollution poses a potential threat to soil organisms: Insights from a global meta and machine-learning analysis - Haiyi Zhang; Tianhao Che; Hongwen Yu; Jing Yue; Quanying Wang (Environmental Research, 2026)

Phenol exposure promotes tumor-related signaling and blood vessel formation through the extracellular signal-regulated kinase/p38/hypoxia-inducible factor-1α pathway in cellular and zebrafish models - Chung-Yu Lin; Wangta Liu; Pei-Hsuan Chen; Chia C. Wang; Che-Hsin Lee (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Auditory-perception-based tuneable noise control approach for improving acoustic comfort and behaviour of autistic individuals in indoor/outdoor environments - Tak Chun Kwong; Steve Wai Yin Mung; Huan-Ling Yuan; Henry Kar Hang Chu; Yuen Yi Cynthia Lai; Chetwyn Che Hin Chan; Ho Man Yu; Yat Sze Choy (Building and Environment, 2026)

Long-term retrieval and analysis of aerosol components and optical properties in Tianjin, China: Insights from GRASP/component approach and sun-photometer observations (2014–2024) - Xindan Zhang; Lei Li; Yu Zheng; Jibiao Zhu; Tiantao Cheng; Ke Gui; Yuanxin Liang; Shuhui Liu; Haoling Zhang; Jingrui Ma; Huizheng Che; Xiaoye Zhang (Atmospheric Research, 2026)

mRNA Rather than Protein Expression of Hepatic Selenoprotein H is More Sensitive to Short-term Low Aflatoxin B1 Exposure in Mice with Varying Selenium Intake - Ruirui Yu; Mengru Hao; Aiping Liu; Chenggang Yang; Ping Xu; Yong Zhou; Alexey A. Tinkov; Aolin Yang; Qingqing Lv; Ziyu Han; Chao Wang; Zhou Wang; et al. (Biological Trace Element Research, 2026)

Discovery of a potential CERS2 inhibitor: hit compound identification via structure—based virtual screening and molecular dynamics simulations - Boming Yu; Shenlong Mo; Yu Chen; Yaoguang Hua; Tong Che; Jin Zhang; Anthony H. Futerman; Jingjing Duan (Molecular Diversity, 2026)

Molecular identification and characterization of a ‘Candidatus phytoplasma australasiaticum’ -related strain associated with Scaevola taccada virescence disease in China - Hai-Yan Che; Mei-Jiao Hu; Hai-Bo Long; Da-Quan Luo; Shao-Shuai Yu (Physiological and Molecular Plant Pathology, 2026)

Kinetic control of phase inversion assembles mesoporous silica at membrane interfaces for high-affinity tetrabromobisphenol A recognition and membrane antifouling - Chao Yu; Daoyue Xie; Yilin Wu; Huinan Che; Yanhui Ao (Chemical Engineering Journal, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

Boosting catalytic activity toward industrial water electrolysis: Ag–triggered dual–site activation in NiFe LDH for ultra–efficient oxygen evolution reaction - Habib Gemechu Edao; Chia-Yu Chang; Woldesenbet Bafe Dilebo; Chemeda Barasa Guta; Keseven Lakshmanan; Endalkachew Asefa Moges; Fikiru Temesgen Angerasa; Baru Debtera Bejena; Chun-Chi Chang; Wei-Sheng Liao; Meng-Che Tsai; Wei-Nien Su; et al. (Chemical Engineering Journal, 2026)

Comparative impact of surface reflection models on aerosol component retrieval - Shuhui Liu; Lei Li; Xindan Zhang; Cheng Chen; Haoling Zhang; Ke Gui; Yu Zheng; Jingrui Ma; Huizheng Che (Atmospheric Research, 2026)

Engineering Mesenchymal Stem Cell-Derived Extracellular Vesicles for the Treatment of Chronic Kidney Diseases - Hsiu-Jung Liao; Kai-Hsiang Shu; Wei-Che Yu; Yen-Ling Chiu (Tissue Engineering and Regenerative Medicine, 2026)

Exosome Purification Strategy Influences the Regenerative Efficacy of Dental Pulp Stem Cell-Derived Exosomes in Bone Regeneration - Borae Lee; Chia-Yi Hung; Yu-Ting Chien; Chi-Che Hsieh; Wei-Hao Cheng; Ya-Hui Chan; Pin-Chuang Lai; Sheng-Wei Feng (Stem Cell Reviews and Reports, 2026)

Decoding adenomyosis pathogenesis using an assembloid model - Yiliang Xu; Tao Cheng; Jianzhang Wang; Zhiruo Qiu; Xiaohong Guan; Yayuan Yu; Jiacheng Shen; Fangfang Xu; Xiaohong Jiang; Dandan Bai; Mingzhu Wang; Shuyan Mei; et al. (Science China Life Sciences, 2026)

Integrating structural equation modeling and machine learning to unravel the drivers of fine-grained urban thermal patterns - Ying Ding; Chen Huang; Jue-Yu Lin; De-Shun Xu; Yang-Zi Che; Ying Sun; Wei-Lin Liao (Urban Climate, 2025)

Aerosol reductions boost near-term warming rate in a plausible net-zero transition - Yadong Lei; Zhili Wang; Junting Zhong; Xiaochao Yu; Huizheng Che; Xiaoye Zhang (Science Bulletin, 2025)

Long-term substitution of chemical fertilizer with organic manure enhances the activity and autotrophic growth of ammonia-oxidizing archaea and comammox nitrospira in paddy soil - Chunyan Wu; Xu Tang; Che Tan; Tao Sun; Yu Zeng; Yinxiu Liu; Yingxia Liu; Yan Li; Yongchao Liang; Chang Yin (Journal of Environmental Management, 2025)

Combined toxicity of microplastics and heavy metals to terrestrial plants: A global meta-analysis integrating machine learning predictions - Ye-Qian Zhen; Tian-Hao Che; Yu-Xuan Song; Ya-Ming Wan; Hai-Han Jiang; Zuo-Zhou Yu; Miao Yu; Shi-Qi Xu; Cheng-Yong Li; Jing-Ya Zhou (Journal of Environmental Chemical Engineering, 2025)

Machine learning-integrated SERS platform based on Au Se nanowires for indigo carmine detection in real samples - Nazar Riswana Barveen; Che-Wei Zeng; Yu-Wei Cheng (Food Chemistry, 2025)

Live GABA-producing and heat-killed probiotic consortium improves sleep and modulates inflammation in an anesthesia- and caffeine-induced sleep disturbance model - Zhen-Shu Liu; Yu-Jie Yang; Cheng-Che Tsai; Yu-Tang Tung; Po-Wen Chen (Food Bioscience, 2025)

Development of risk-based critical limits in HACCP plans through quantitative microbial risk assessment: Salmonella risk in a poultry meat supply chain case in Taiwan - Che-Lun Mai; Yu-Hao Chou; Kelvin Chou; Fang-Jing Song; Hsin-I Hsiao (Food Control, 2025)

Biomimetic adhesive-free self-splicing enables scalable wood film for programmable hygromorphic soft actuators - Wenbo Che; Yufeng Miao; Yifan Liu; Runxuan Wang; John Moyo; Youming Yu; Wenhui Bao; Yunyan Peng (Chemical Engineering Journal, 2025)

Water use strategies of Platycladus orientalis under diverse water management approaches in the western Loess Plateau: Insights from stable isotope analysis - Yu Zhang; Mingjun Zhang; Yuquan Qiang; Rui Lu; Cunwei Che; Shengjie Wang (Plant and Soil, 2025)

Natural and anthropogenic drivers of salinization in the Bohai Rim: Mechanisms and remediation through pine needle amendments - Baijun Shang; Feng Wang; Tong Li; Zhihong Xu; Bernhard Wehr; Yash P. Dang; Rongxiao Che; Lizhen Cui; Jintong Liu; Hui Gao; Shuhui Yu; Tonggang Fu (Journal of Soils and Sediments, 2025)

High Quality, Granular, Timely, Trustworthy and Efficient Vertebrate Species Distribution Data Across a 30,000 km 2 Protected Area Complex - Yinqiu Ji; Alex Diana; Xueyou Li; Eleni Matechou; Jim E. Griffin; Shuwei Liu; Mingjie Luo; Chunying Wu; Ru Bai; Chenyang Yao; Tingting Yin; Feng Dong; et al. (Ecology Letters, 2025)
The routine generation of species distribution data at scale remains a challenge. We used aquatic environmental DNA metabarcoding to sample vertebrate species across the 30,000 km 2 Gaoligongshan region along the China–Myanmar border. In just 56 calendar days (33 researcher‐field‐days + 69 researcher‐lab‐days), we detected 389 vertebrate species, of which 35 are Red‐Listed. We introduce the ‘eDNA‐aware’ OccPlus occupancy model, which accounts for false‐negative and false‐positive error in the field and lab. OccPlus leverages the taxonomic breadth of eDNA datasets by using ordination to estimate species occupancies. We recover known biogeographic patterns and find that native terrestrial and fish species have higher occupancies inside protected areas while domesticated species and non‐native fishes have higher occupancies outside them. Our study demonstrates how eDNA metabarcoding can obtain high‐quality, granular, timely, trustworthy and efficient species distribution data to facilitate nature conservation and restoration.

Novel insight into the heavy metal immobilization by coal fly ash-based geopolymers using machine learning and density functional theory - Kaizhi Yang; Bo Yang; Kezhou Yan; Yining Su; Longyi Zhao; Jungang Tang; Yu Che; Yanxia Guo (Waste Management, 2025)

Runup and inundation of non-decaying dam-break bores on rough uniform slopes - Yun-Ta Wu; Yu-Che Huang (Ocean Engineering, 2025)

Outbreeding of isofemale lines as a candidate approach to improve the quality of thelytokous Wolbachia-infected line of the egg parasitoid, Trichogramma dendrolimi Matsumura (Hymenoptera: Trichogrammatidae - Hong-Yu Liang; Ying Shan; Qian-Jin Dong; Jin-Cheng Zhou; Xiao-Hui Ma; Li-Sheng Zhang; Wu-Nan Che; Hui Dong (Journal of Invertebrate Pathology, 2025)

Dynamic relationships of antibiotic resistomes and greenhouse gas-functioning microbes across diverse habitats - Meiping Chen; Lu Song; Chen Ye; Hans-Peter Grossart; Yuyi Yang; Siyue Li; Hao Liao; Yu Gong; Rongxiao Che; Quanfa Zhang (Environmental Research, 2025)

Investigation of the impact of local tumor phenolic-chemistry for dual starvation and vaccination therapy - Jingsong Lu; Zhenhu Guo; Sumei Chen; Ying Li; Xin Xu; Jing Yu; Shenglei Che; Guifeng Zhang; Wensheng Xie; Yen Wei; Lingyun Zhao (Chemical Engineering Journal, 2025)

Decisive electrocatalyst of oxyphilic transition metals with bivalent metal perovskites: Localized oxygen confinement for enhanced 2e-WOR in H₂O₂ production - Chemeda Barasa Guta; Chia-Yu Chang; Fikiru Temesgen Angerasa; Baru Debtera Bejena; Habib Gemechu Edao; Woldesenbet Bafe Dilebo; Endalkachew Asefa Moges; Meng-Che Tsai; Wei-Nien Su; Bing Joe Hwang (Chemical Engineering Journal, 2025)

Synergistic ferroptosis-immunotherapy nanoassembly via PROTAC-mediated SLC7A11 degradation and trisulfide-driven glutathione depletion for enhanced antitumor efficacy - Zhenjie Wang; Yuehua Wang; Yilan Dai; Wenjia Zhang; Chunmei Luo; Siyao Che; Dixian Luo; Jiasi Zhang; Li Deng; Zhiqiang Yu (Chemical Engineering Journal, 2025)

Long-term variations in aerosol optical properties in Beijing: insights from diurnal and nocturnal continuous measurements - Shiya Peng; Yu Zheng; Lei Li; Ke Gui; Jibiao Zhu; Shuhui Liu; Haoling Zhang; Hujia Zhao; Huizheng Che; Xiaoye Zhang (Atmospheric Environment, 2025)

Machine learning of lithium and gallium accumulation based on the major element contents in coal gangue from Shanxi province coalfields - Kezhou Yan; Longyi Zhao; Kaizhi Yang; Yu Che; Yanxia Guo; Fangqin Cheng (Applied Geochemistry, 2025)

A lightweight method for apple disease segmentation using multimodal transformer and sensor fusion - Yihong Song; Manzhou Li; Zizhe Zhou; Jiahe Zhang; Xiangge Du; Min Dong; Qinhong Jiang; Che Li; Yuantao Hu; Qiulin Yu; Dongmei Wang; Hegan Dong; et al. (Computers and Electronics in Agriculture, 2025)

Sodium silicate complex reduces subdermal hemorrhage and prolongs survival after envenomation by Trimeresurus stejnegeri stejnegeri - Yen-Chia Chen; Hao-Ming Chang; Chang-Chih Ke; Chia-Chun Liu; Yu-Kai Huang; Kun-Che Chang; Min-Hui Chen; Isaac Chun-Jen Chen; Yu-Wei Chiang; Po-Yu Liu; Chih-Sheng Lai; Kuo-Lung Lai; et al. (Toxicon, 2025)

Chemical structure and bioactivities of a sulfated polysaccharide from precious medicinal fungi - Mei-Kuang Lu; Chi-Hsein Chao; Tsu-Yuan Chang; Ming-Che Cheng; Yu-Chi Hsu; Chia-Chuan Chang (Phytochemistry Letters, 2025)

Local collaboration between oxygen vacancy, palladium and platinum trimer triggers exceptional performance in the alkaline fuel cell - Dinesh Bhalothia; Che Yan; Yawei Wu; Jui-Cheng Kao; Yu-Chieh Lo; Haolin Li; Nozomu Hiraoka; Hirofumi Ishii; Yen-Fa Liao; Sheng Dai; Chen-Hao Wang; Alice Hu; et al. (Chemical Engineering Journal, 2025)

Interfacial engineering meets process optimization: Highly stable silicon-graphite anodes via pre-calendering polyvinylidene difluoride-MgO coatings - Chu-Chun Lin; Cheng-Che Chien; Yu-Ting Weng; Chia-Chen Fang; Nae-Lih Wu; Rainer Adelung; Mozaffar Abdollahifar; Ryo Takata; Carlos Eduardo Alarcón-Suesca; Franz Schmidt (Chemical Engineering Journal, 2025)

Multi-level metalized PBO composite fabric for polar extreme environments: integrating electromagnetic protection, stable electric thermal conversion, and high-strength - Che Zhou; Dan Yu; Canglong Xing; Zhichao Zhu; Zeyu Yang; Xinhai He; Tao Fu; Zhongxiao Song; Wei Fan; Dongzhen Chen (Chemical Engineering Journal, 2025)

Factors influencing the relationships between hourly visibility and aerosol optical depth in China—implications for hourly aerosol optical depth retrievals using automatic visibility observations - Nanxuan Shang; Ke Gui; Tiantao Cheng; Hengheng Zhao; Xutao Zhang; Wenrui Yao; Yu Zheng; Lei Li; Yurun Liu; Hong Wang; Zhili Wang; Huizheng Che; et al. (Atmospheric Environment, 2025)

Inhibition of PERK-eIF2α-ATF4 signaling enhances the antiviral effects of resveratrol-loaded nanoparticles against enterovirus 71 in hand, foot, and mouth disease - Bin Wang; Lihe Che; Peng Zhang; Luyao Sun; Yue Yu; Na Du (Archives of Virology, 2025)

Research progress on programmed cell death of cardiomyocytes in pressure-overload hypertrophic cardiomyopathy - Fei Xiao; Hui-Li Li; Jia-Rui Wang; Hui-Min Wu; Yu-Qi Cai; Jia-Wan Wang; Hao Che; Gang Li; Zheng-Yuan Xia; Yu-Bo Xie; Sheng Wang (Apoptosis, 2025)

Atmospheric emerging pollutants of cyclic volatile methyl siloxanes across the Yangtze River Delta region revealed by mobile measurements - Lin Cheng; Yunhua Chang; Haifeng Yu; Xiang Che; Wen Tan; Liang Zhu (Chemosphere, 2025)

Feasibility and limitations of using specific nitrification inhibitors to differentiate ammonia oxidizer activity - Che Tan; Yu Zeng; Cécile Gubry-Rangin; Chang Yin; Yongchao Liang (Soil Biology and Biochemistry, 2025)

Corrigendum to “Molecular mechanism governing RNA-binding property of mammalian TRIM71 protein” [Sci. Bull. 69(1) (2024) 72–81] - Fandi Shi; Kun Zhang; Qixuan Cheng; Shiyou Che; Shuxin Zhi; Zhenyu Yu; Fei Liu; Feifei Duan; Yangming Wang; Na Yang (Science Bulletin, 2025)

Nonlinear dynamics and vibration mechanisms in air scroll compressors: A study on orbiting and fixed scroll pair - Xiao-Liang Yang; Bin Peng; Ming-Lang Che; Jian-Fei Shi; Zhi-Xiang Liao; Yu-Bo Zhang (International Journal of Refrigeration, 2025)

Spatiotemporal dynamics of histone H3K27 demethylase during development - Yu-Chen Tsai; Yun-Chen Chung; Cheng-Chan Yang; Cheng-Hsien Lee; Che-Wei Liu; Shih-Ming Huang; Lan-Hsin Wang (Insect Biochemistry and Molecular Biology, 2025)

Corrigendum to “Modulating the density of Co3N/CFs active site by optimizing the micro-structure for overall water splitting electrocatalysis” [Chem. Eng. J. 515 (2025) 163505] - Qiusen Liu; Tingzheng Fu; Hongbiao Xiao; Ye Yu; Zhiqing Che; Yixing Zhang; Anran Chen; Mian Li; Tingting Liu (Chemical Engineering Journal, 2025)

Intermediate water engineering in wood hydrogels for ultra-low enthalpy solar desalination - Shutong Zhang; Yunyan Peng; Xiaolong Xu; Jingqing Sun; Jiawei Lu; Yi Zhang; Wenbo Che; Youming Yu (Chemical Engineering Journal, 2025)

Bimetallic ion crosslinked hydrogels sequentially releasing immunomodulatory factors and osteogenic factors to promote bone integration of 3D printed titanium alloy prostheses - Xiao Sheng; Zhenjia Che; Chuncheng Shen; Jingtao Wu; Chenhao Qiu; Chenjie Tan; Junjie Mao; Bo Li; Hang Yu; Jianyou Li; Wei Liu; Chen Li; et al. (Chemical Engineering Journal, 2025)

Determination of the deposition of urban submicron aerosols in the human respiratory tract considering hygroscopic growth - Aoyuan Yu; Jiayuan Lu; Xiaojing Shen; Xinyao Hu; Yangmei Zhang; Quan Liu; Hongfei Tong; Linlin Liang; Lei Liu; Qianli Ma; Lujie Han; Huizheng Che; et al. (Atmospheric Environment, 2025)

Real-time assessment of PM1.0-bound trace metal cancer risk through high-resolution GED-ICP-MS and integrated ELCR analysis - Li-Ti Chou; Yi-Pin Lin; Chia-Hung Yu; Jun-Fa Ye; Wen-Che Hou; Ta-Chih Hsiao (Journal of Hazardous Materials, 2025)

Multi-objective optimization of inlet and outlet in a circular culture fish tank using the GBDT-NSGAII algorithm and computational fluid dynamic - Shanhong Zhang; Guanghui Yu; Yu Guo; Yang Wang; Daoliang Li; Xiaoli Zhao; Dannie D. O'Brien; Jui-Che Chiang (Aquacultural Engineering, 2025)

A lignin-wood Janus membrane with three-dimensional interconnected layered micro/nano channels for on-demand separation of surfactant-stabilized oil/water emulsions - Yifan Liu; Yufeng Miao; Zhuo Huang; Runxuan Wang; Yunyan Peng; Xiaolong Fang; Wenbo Che; Youming Yu (Desalination, 2025)

Modulating the density of Co3N/CFs active site by optimizing the micro-structure for overall water splitting electrocatalysis - Qiusen Liu; Tingzheng Fu; Hongbiao Xiao; Ye Yu; Zhiqing Che; Yixing Zhang; Anran Chen; Mian Li; Tingting Liu (Chemical Engineering Journal, 2025)

The significance of organophosphate flame retardants in patients with esophageal squamous cell carcinoma - Hung-I Lu; Wan-Ting Huang; Wen-Chin Lee; Fu-Jen Cheng; Chia-Te Kung; Chin-Chou Wang; Liang-Jen Wang; Yu-Che Ou; Shau-Hsuan Li (Environmental Geochemistry and Health, 2025)

Immobilization of Pb in Alkaline Soil Amend with Nano-hydroxyapatite: Speciation, Bioavailability, and Bioaccessibility - Kai Che; Jinxing Yu; Yukun Ju; Xuan Zhao; Yunqian Gong; Chongming Chen (Bulletin of Environmental Contamination and Toxicology, 2025)

Corrigendum to “Improved entropy-CRITIC population model based on temporal and spatial variability: Construction and application in wastewater epidemiology” [Sci. Total Environ. 958 (2025) 177807] - Xinfeng Che; Xiaoyu Zheng; Wenjia Tao; Yu Zhang; Peipei Liu; Bin Di; Hongwei Qiao (Science of The Total Environment, 2025)

Investigating the impact of fecal contamination on antibiotic resistance genes in urban environments using host-associated molecular indicators - Yujing Duan; Hui She; Lingna Jing; Lianrui Duan; Jinxiu Zheng; Ying Shao; Yuxin Che; Yu Shi; Chao Guo; Wenhui Zhao; Tao Yang; Lijun Yang (Environmental Pollution, 2025)

Field experiment study to assess critical wave conditions leading to failure of mangrove Rhizophora stylosa - Nobuhito Mori; Che-Wei Chang; Kenji Ono; Hironori Noguchi; Shigeyuki Baba; Hideaki Yanagisawa; Toyohiko Miyagi; Naoki Tsuruta; Kojiro Suzuki; Shiro Yamagata; Yusuke Hasegawa; Yu-Lin Tsai; et al. (Coastal Engineering, 2025)

Using unmanned aerial vehicle monitoring for the landslide and dammed lake: a case study of the Xiuluan area in Taiwan - Che-Hsin Liu; Jui-Yi Ho; Horn-Ru Liao; Shih-Chiang Lee; Naoki Sakai; Chen-Yu Chen; Chih-Hsin Chang (Bulletin of Engineering Geology and the Environment, 2025)

Experimental study of pressure distribution and wave forces on pile groups under extreme waves - Xi Yu; Jiajia Wang; Wanshui Han; Lili Xiao; Xin Xu; Kai Zhou; Silu Che; Xiaokun Chen; Mengqi Xia (Ocean Engineering, 2025)

Single-step pyrolytic synthesis of ultra-microporous ammonialized biochar for carbon dioxide capture - Che-Jung Hsu; I-Lin Kuo; Hsing-Cheng Hsi; Su Shiung Lam; Ying-Pin Huang; Yu-Chieh Ting (Journal of Environmental Management, 2025)

Developing hydrothermal stable SAPO-11 catalysts to convert glucose into 5-HMF - Yutong Che; Peng Lu; Jinlei Zhang; Xiaosheng Wang; Yukang Liu; Hailong Yu; Yuxiang Liu (Fuel, 2025)

High content heteroatoms doped and valuable biomass derived activated carbon composited with graphene for high performance supercapacitors - Ming-Che Cheng; Yu-Sung Chang; Du-Cheng Tsai; Yen-Lin Huang; Fuh-Sheng Shieu (Fuel, 2025)

Risks of respiratory and circulatory system diseases induced by exposure to PM2.5 in high humidity and low solar radiation environments: disease types, genes, and functions - Xiaomeng Li; Liru Zhang; Zhengliang Zhang; Xuan Li; Jingli Qian; Jiawei Zhou; Hanxiong Che; Yan Han; Xin Qi; Fumo Yang; Yu Huang; Chao Peng; et al. (Environmental Geochemistry and Health, 2025)

Deciphering the microbiome, lipopolysaccharides, and metabolome interplay: Unveiling putrescine's mechanism for enhancing sperm quality in heat-stressed boars - Chenglong Yu; Hao Li; Lun Hua; Lianqiang Che; Bin Feng; Zhengfeng Fang; Shengyu Xu; Yong Zhuo; Jian Li; De Wu; Junjie Zhang; Yan Lin (Theriogenology, 2025)

Rent-seeking behavior of ship sulfur emission detection based on evolutionary game theory - Jing Liang; Liang Dong; Yuhang Che; Yu Tang; Yuying Dou (Regional Studies in Marine Science, 2025)

Mercury pollution control and Marphysa sanguinea bio-response in active-capped sediment with calcium alginate/activated carbon composite - Che-Jung Hsu; Ying-Chu Wang; Adrienne Chung; Cheng-Di Dong; Chiu-Wen Chen; Yu Ting; Hsing-Cheng Hsi (Journal of Hazardous Materials, 2025)

Selective preparation of aromatic compounds from catalytic pyrolysis polyester coating over Ni, Mo and Co metal modified ZSM-5 - Zhen-Qiang Yu; Yao-Xin Xiao; Dong Liang; Che Zhao; Zhen Huang; Gang-Qi Cheng; Rui Shan; Hao-Ran Yuan; Yong Chen (Journal of Environmental Chemical Engineering, 2025)

Perinone with fast proton insertion chemistry for durable aqueous zinc battery - Yixiao Yang; Qing Lang; Jian Zhang; Jiayuan Yu; Jiulong Che; Qi Fan; Kun Liang; Gang Wang (Chemical Engineering Journal, 2025)

Boosting photocatalytic hydrogen evolution from binary mixture of hydrophilic-hydrophobic conjugated polymer dots with variable saponification degrees and molecular weights - Khanh Do Gia Huynh; Yu-Ting Huang; Meng-Che Tsai; Islam M.A. Mekhemer; Jayachandran Jayakumar; Yu-Tung Lin; Chun-Hao Li; Swatilekha Pratihar; Tse-Fu Huang; Dung Chau Kim Hoang; Shang-Da Yang; Ho-Hsiu Chou; et al. (Chemical Engineering Journal, 2025)

Displacement evolution of failure and non-failure sliding rock slopes - Hsien-Li Kuo; Guan-Wei Lin; Ting-Yu Lin; Che-Hsin Liu; Chung-Ray Chu; Chih-Hsin Chang; Ching-Weei Lin; Hongey Chen (Landslides, 2025)

Development and characterization of novel wood-based composite materials for solar-powered atmospheric water harvesting: A machine intelligence supported approach - Xingying Zhang; Yangyang Xu; Shenjie Han; Xiang Weng; Wenbo Che; Kongjie Gu; Ying Guan; Youming Yu; Derek Hao; Junfeng Hou (Journal of Cleaner Production, 2025)

Comparative analysis of fecundity related traits and transcriptome in two isofemale lines of the egg parasitoid, Trichogramma dendrolimi (Matsumura) - Hong-Yu Liang; An-Ke Liu; Ning He; Jin-Cheng Zhou; Xiao-Hui Ma; Li-Sheng Zhang; Wu-Nan Che; Hui Dong (Journal of Asia-Pacific Entomology, 2025)

The optimized nitrogen rate reduced ammonia emissions from rice paddies in the cold region of Northeast China - Shiting Bi; Pengfei Li; Jiarui Lv; Qiang Dong; Xiangyu Luo; Yeqi Che; Muhammad Rehman Naseer; Zhilei Liu; Cailian Yu; Xianlong Peng (European Journal of Agronomy, 2025)

Long-term distribution and evolution trends of absorption aerosol optical depth with different chemical components in global and typical regions - Hujia Zhao; Ke Gui; Yangfeng Wang; Yaqiang Wang; Hong Wang; Yu Zheng; Lei Li; Xiaofang Jia; Huizheng Che; Xiaoye Zhang (Atmospheric Research, 2025)

Comprehensive validation of a compact laser speckle contrast imaging system for vascular function assessment: from the laboratory to the clinic - Meng-Che Hsieh; Chia-Yu Chang; Ching-Han Hsu; Congo Tak Shing Ching; Lun-De Liao (Medical & Biological Engineering & Computing, 2025)

Increased miRNA-375 causes oxidative damage but promotes apoptosis resistance and cell migration in the clam Ruditapes philippinarum - Ming Cong; Zhaoshun Li; Wenwen Tian; Yixian Yu; Yu Che; Jiasen Lv (Frontiers in Marine Science, 2025)
MicroRNA is an important regulatory factor at the post-transcriptional level. Previous miRNAomics analysis found that miRNA-375 was steadily upregulated in the clam Ruditapes philippinarum upon ammonia nitrogen exposure. However, we have no knowledge about its regulatory mechanism yet. In this study, the clams were challenged by the injection of miRNA-375 mimics/inhibitor in vivo . Then, a combined approach of qRT-PCR, enzyme assay, and ultrastructure observation was applied to investigate its regulatory effects on the related genes, cellular parameters, and histological structures, respectively. Results showed that increased expression of miRNA-375 interfered with the expression levels of both its target genes and ammonia toxicity-related genes, which would probably lead to oxidative stress, migration of damaged cells, apoptosis resistance, and increased possibility of tumor formation. In addition, miRNA-375 increased MDA content but decreased glutamate content and caused serious structure damage to the clam gills. Thus, increased miRNA-375 probably brings a disastrous fate to the clam R. philippinarum by inducing oxidative damage but promoting apoptosis resistance and cell migration. Overall, this study revealed for the first time the regulatory effects of miRNA-375 in the clams and gave valuable clues to understand the toxicological mechanisms of ammonia nitrogen on the marine bivalve.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Using Gaussian Mixture Model Clustering for the Automated Segmentation of Cerebral Arteriovenous Malformations in Magnetic Resonance Images - Ting-Yu Lin; Cheng‑Chia Lee; Yu-Wei Chen; Hsiu-Mei Wu; Ching-Jen Chen; Huai-Che Yang; Syu-Jyun Peng (Journal of Medical and Biological Engineering, 2025)

Improved entropy-CRITIC population model based on temporal and spatial variability: Construction and application in wastewater epidemiology - Xinfeng Che; Xiaoyu Zheng; Wenjia Tao; Yu Zhang; Peipei Liu; Bin Di; Hongwei Qiao (Science of The Total Environment, 2025)

A comprehensive molecular phylogeny of the genus Sylvirana (Anura: Ranidae) highlights unrecognized diversity, revised classification and historical biogeography - Yun-He Wu; Man-Hao Xu; Chatmongkon Suwannapoom; Sang Ngoc Nguyen; Robert W. Murphy; Theodore J. Papenfuss; Amy Lathrop; Felista Kasyoka Kilunda; Wei Gao; Zhi-Yong Yuan; Jin-Min Chen; Liang Zhang; et al. (Molecular Phylogenetics and Evolution, 2025)

Phototunable phosphorescence energy transfer based on photodimerization of coumarin-12-crown-4 accelerated by γ-cyclodextrin - Hui-Juan Wang; Yan-Tao Li; Ming-Che Shao; Chang-Shuo Yu; Jin-Yao Yang; Lingyang Liu; Suna Wang; Jianmin Dou (Chemical Engineering Journal, 2025)

Editing of the soluble starch synthase gene MeSSIII-1 enhanced the amylose and resistant starch contents in cassava - Xiaohua Lu; Yajie Wang; Xinghou Zhen; Yannian Che; Hui Yu; Yujian Ge; Xiangwen Wang; Ruimei Li; Mengting Geng; Bin Zhou; Jiao Liu; Jianchun Guo; et al. (Carbohydrate Polymers, 2025)

Performance of Convolutional Neural Network Models in Meningioma Segmentation in Magnetic Resonance Imaging: A Systematic Review and Meta-Analysis - Ting-Wei Wang; Jia-Sheng Hong; Wei-Kai Lee; Yi-Hui Lin; Huai-Che Yang; Cheng-Chia Lee; Hung-Chieh Chen; Hsiu-Mei Wu; Weir Chiang You; Yu-Te Wu (Neuroinformatics, 2024)
Background Meningioma, the most common primary brain tumor, presents significant challenges in MRI-based diagnosis and treatment planning due to its diverse manifestations. Convolutional Neural Networks (CNNs) have shown promise in improving the accuracy and efficiency of meningioma segmentation from MRI scans. This systematic review and meta-analysis assess the effectiveness of CNN models in segmenting meningioma using MRI. Methods Following the PRISMA guidelines, we searched PubMed, Embase, and Web of Science from their inception to December 20, 2023, to identify studies that used CNN models for meningioma segmentation in MRI. Methodological quality of the included studies was assessed using the CLAIM and QUADAS-2 tools. The primary variable was segmentation accuracy, which was evaluated using the Sørensen–Dice coefficient. Meta-analysis, subgroup analysis, and meta-regression were performed to investigate the effects of MRI sequence, CNN architecture, and training dataset size on model performance. Results Nine studies, comprising 4,828 patients, were included in the analysis. The pooled Dice score across all studies was 89% (95% CI: 87–90%). Internal validation studies yielded a pooled Dice score of 88% (95% CI: 85–91%), while external validation studies reported a pooled Dice score of 89% (95% CI: 88–90%). Models trained on multiple MRI sequences consistently outperformed those trained on single sequences. Meta-regression indicated that training dataset size did not significantly influence segmentation accuracy. Conclusion CNN models are highly effective for meningioma segmentation in MRI, particularly during the use of diverse datasets from multiple MRI sequences. This finding highlights the importance of data quality and imaging sequence selection in the development of CNN models. Standardization of MRI data acquisition and preprocessing may improve the performance of CNN models, thereby facilitating their clinical adoption for the optimal diagnosis and treatment of meningioma.

Partial organic substitution increases soil quality and crop yields but promotes global warming potential in a wheat-maize rotation system in China - Gong Wu; Hai-meng Huang; Bei-bei Jia; Lei-lei Hu; Chong-sheng Luan; Qi Wu; Xiao-yu Wang; Xiao-xiao Li; Zhao Che; Zhao-rong Dong; He Song (Soil and Tillage Research, 2024)

Impacts of micro/nano plastics on the ecotoxicological effects of antibiotics in agricultural soil: A comprehensive study based on meta-analysis and machine learning prediction - Tian-Hao Che; Guan-Kai Qiu; Hong-Wen Yu; Quan-Ying Wang (Science of The Total Environment, 2024)

Characteristics and health risks assessment of PM2.5-bound heavy metals during winter in urban areas of northern China: A case study in Kaifeng - Xin Qi; Yan Han; Hanxiong Che; Jiawei Zhou; Chao Peng; Zhier Bao; Yiliang Liu; Lingshuo Meng; Shumin Zhang; Fumo Yang; Wenbo Xue; Yu Lei; et al. (Science of The Total Environment, 2024)

Comparison of environmental impacts from pyrolysis, gasification, and combustion of oily sludge - Hongdi Yu; Fawei Lin; Xuan Guo; Chujun Luan; Jiantao Li; Rundong Li; Lei Che; Wangyang Tian; Guanyi Chen (Journal of Hazardous Materials, 2024)

Plasmonic Au-NPs photodecorated on NiCoLDH nanosheets as a flexible SERS sensor for the real-time detection of fipronil - Nazar Riswana Barveen; Sathishkumar Chinnapaiyan; Che-Wei Zeng; Chi-Hsien Huang; Yen-Yu Lin; Yu-Wei Cheng (Journal of Hazardous Materials, 2024)

Identification of soybean mosaic virus strain SC7 resistance loci and candidate genes in soybean [Glycine max (L.) Merr.] - Yixiang Pu; Rujuan Yan; Dongbing Jia; Zhijun Che; Rufei Yang; Changyun Yang; Hui Wang; Hao Cheng; Deyue Yu (Molecular Genetics and Genomics, 2024)

Organic carbon decomposition temperature sensitivity positively correlates with the relative abundance of copiotrophic microbial taxa in cropland soils - Yuan Du; Anlan Yu; Yuan Chi; Zelin Wang; Xinrui Han; Kaifang Liu; Qiuping Fan; Xin Hu; Rongxiao Che; Dong Liu (Applied Soil Ecology, 2024)

Standardization in global environmental antibiotic resistance genes (ARGs) surveillance - Xuemei Mao; Xiaole Yin; Yu Yang; You Che; Xiaoqing Xu; Yu Deng; Liguan Li; Tong Zhang (Critical Reviews in Environmental Science and Technology, 2024)

Fungal necromass contribution to carbon sequestration in global croplands: A meta-analysis of driving factors and conservation practices - Dong Liu; Ziyan Zhou; Shahid Iqbal; Ting Ting Dou; Gregory Bonito; Wei Liu; Shaoshan An; Caspar C.C. Chater; Jesus Perez-Moreno; Rongxiao Che; Davey L. Jones; Fuqiang Yu (Science of The Total Environment, 2024)

Terrestrial locomotion stability of undulating fin amphibious robots: Separated elastic fin rays and asynchronous control - Deliang Yu; Tianyu Che; Huibo Zhang; Yezhuo Li; Dongyang Sun; Zhaotian Wang (Ocean Engineering, 2024)

Copper/iron bimetal phenolic networks boosted apoptosis/ferroptosis/cuproptosis combined tumor therapy through dual glutathione depletion - Fan Zhao; Hongyan Yu; Chen Wang; Junchen Xu; Hao Gao; Yao Ying; Wangchang Li; Juan Li; Jingwu Zheng; Liang Qiao; Shenglei Che; Jing Yu (Chemical Engineering Journal, 2024)

Design of a portable bioassay system based on highly efficent nanozyme and Au-DNA nanocluster: Toward current/colorimetric dual-signal detection of sugarcane smut - Danyao Tang; Zeping Wang; Rongshuai Che; Jie Liao; Meixin Yan; Xiaoqiu Zhang; Jun Yan; Ke-Jing Huang; Xuecai Tan; Yu Ya (Chemical Engineering Journal, 2024)

Experimental investigation on product and temperature distribution in a continuous flow packed-bed reactor for dodecahydro-N-ethylcarbazole dehydrogenation - Jingwen Xue; Pengzhao Li; Pengfei Yu; Jinhao Yi; Tao Ma; Hu Liu; Defu Che (Chemical Engineering Journal, 2024)

Novel electrocatalyst with abundant oxygen vacancies enabling efficient two-electron water oxidation reaction for H2O2 synthesis - Chemeda Barasa Guta; Habib Gemechu Edao; Woldesenbet Bafe Dilebo; Chia-Yu Chang; Fikiru Temesgen Angerasa; Endalkachew Asefa Moges; Yosef Nikodimos; Keseven Lakshmanan; Meng-Che Tsai; Wei-Nien Su; Bing Joe Hwang (Chemical Engineering Journal, 2024)

Long-term addition of organic manure stimulates the growth and activity of comammox in a subtropical Inceptisol - Yu Zeng; Che Tan; Lei Zhang; Lelin You; Wanning Zheng; Hao Chen; Hongyun Peng; Chunyan Wu; Yongchao Liang (Science of The Total Environment, 2024)

Riboflavin-induced microbial succession for enhanced tellurite reduction in wastewater treatment - Jiawei Jing; Bin Yu; Tingting Wang; Xinyu Guo; Pengfei Huang; Jiayue Che; Chuan Li; Yuanyuan Qu (Journal of Environmental Chemical Engineering, 2024)

Enhanced reductive catalytic fractionation of lignocellulose using a water-resistant RuNiZnOx/Nb2O5 catalyst with synergistic hydrogen spillover and acidic properties - Zhaozhuo Yu; Wenzhuo Kong; Yaping Guo; Wen Liang; Jiawei Liang; Meijuan Chen; Dongxu Zhao; Hongzhen Ma; Xiangjun Liu; Solomon Inalegwu Okopi; Lei Che; Qi Zhang; et al. (Fuel, 2024)

Synergistic Triple-Action morphological composite Anode: Integrating lattice Softening, Interfacial electric Fields, and dual confinement for superior Potassium-Ion battery performance - Jia-Sheng Lin; Yi-Yen Hsieh; Kai-Yuan Hsiao; Yi-Chun Yang; Che-Hung Wang; Ming-Yen Lu; Wen-Wei Wu; Hsing-Yu Tuan (Chemical Engineering Journal, 2024)

Targeting TGFβ receptor-mediated snail and twist: WSG, a polysaccharide from Ganoderma lucidum, and it-based dissolvable microneedle patch suppress melanoma cells - Hung-Chih Lo; Tzu-En Lin; Che-Yu Lin; Wei-Hao Wang; Yu-Chen Chen; Pei-Hsien Tsai; Jung-Chen Su; Mei-Kuang Lu; Wei-Hung Hsu; Tung-Yi Lin (Carbohydrate Polymers, 2024)

The role of ALDH1A1 in glioblastoma proliferation and invasion - Yu-Kai Huang; Tzu-Ming Wang; Chi-Yu Chen; Chia-Yang Li; Shu-Chi Wang; Khushboo Irshad; Yuan Pan; Kun-Che Chang (Chemico-Biological Interactions, 2024)

Regional Aerosol Optical Depth over Antarctica - Lijing Chen; Minghu Ding; Yong She; Lei Zhang; Zhaoliang Zeng; Jiajia Jia; Yu Zheng; Biao Tian; Kongju Zhu; Xin Wang; Zhendong Yao; Huizheng Che (Atmospheric Research, 2024)

Long non-coding RNA FKSG29 regulates oxidative stress and endothelial dysfunction in obstructive sleep apnea - Yung-Che Chen; Po-Yuan Hsu; Mao-Chang Su; Yung-Lung Chen; Ya‐Ting Chang; Chien-Hung Chin; I.-Chun Lin; Yu-Mu Chen; Ting-Ya Wang; Yong-Yong Lin; Chiu-Ping Lee; Meng-Chih Lin; et al. (Molecular and Cellular Biochemistry, 2024)

A review on ‘source prevention, process control, end recovery’ trinity-comprehensive treatment technology for acid mine drainage - Yu Yang; Bo Li; Lulu Che; Menghua Li; Pu Liu; Tao Li; Ye Luo (Process Safety and Environmental Protection, 2024)

Biochar decreases cadmium uptake in indica and japonica rice (Oryza sativa L.): Roles of soil properties, iron plaque, cadmium transporter genes and rhizobacteria - Meiling Xu; Meiling Ren; Yu Yao; Qi Liu; Jing Che; Xiaozhi Wang; Qiao Xu (Journal of Hazardous Materials, 2024)

Optimization and analysis of a novel hydrogen liquefaction coupled system with dual path hydrogen refrigeration cycle and the closed nitrogen cycle pre-cooling - Shipeng Yu; Zhaoxi Wang; Guodong Qiu; Xunjian Che; Jie Chen; Qian Li; Weihua Cai (Journal of Cleaner Production, 2024)

Unraveling novel umami peptides from yeast extract (Saccharomyces cerevisiae) using peptidomics and molecular interaction modeling - Chunyu Gao; Rilei Yu; Xiaomei Zhang; Xue Song; Lizhi Che; Yuying Tang; Jinyue Yang; Jing Hu; Jian Xiong; Xue Zhao; Hongwei Zhang (Food Chemistry, 2024)

Screening and rational identification of a novel angiotensin-converting enzyme C-domain inhibitory peptide from Fabaceae food peptide library - Tin-Yun Ho; Hsin-Yi Lo; Guan-Ling Lu; Chia-Yu Lin; Mei-Li Stevens; Chiao-Che Chen; Chien-Yun Hsiang (Food Chemistry, 2024)

Tunicate cellulose nanocrystal reinforced conductive multi-responsive hydrogel with super flexible, fatigue resistant and self-healable capability for antibacterial flexible sensors - Qin Yang; Mingtao He; Zhongrui Yu; Yijie Liu; Yilan Bai; Tianci Liu; Tingting Wang; Lingtao Meng; Fanjun Meng; Qinglin Ma; Yuju Che (Chemical Engineering Journal, 2024)

Relative contributions of component-segregated aerosols to trends in aerosol optical depth over land (2007–2019): Insights from CAMS aerosol reanalysis - Hengheng Zhao; Ke Gui; Wenrui Yao; Nanxuan Shang; Xutao Zhang; Yuanxin Liang; Yurun Liu; Lei Li; Yu Zheng; Zhili Wang; Hong Wang; Junying Sun; et al. (Atmospheric Environment, 2024)

Insecticide resistance and characteristics of mutations related to target site insensitivity of diamondback moths in Taiwan - Chia-Che Chang; Shu-Mei Dai; Chien-Yu Chen; Li-Hsin Huang; Yu-Hsien Chen; Ju-Chun Hsu (Pesticide Biochemistry and Physiology, 2024)

Enhancing miso production with optimized puffed-rice koji and its biological function evaluation - Shin-Ping Lin; Yu-Chieh Chou; Chiao-En Chen; Yen-Tso Lai; Chen-Che Hsieh; Tsung-Yu Tsai; Yun-Hsin Lin; Shella Permatasari Santoso; Hui-Wen Lin; Kuan-Chen Cheng (Food Bioscience, 2024)

Incorporation of atomic Fe-oxide triggers a quantum leap in the CO2 methanation performance of Ni-hydroxide - Amisha Beniwal; Dinesh Bhalothia; Yin-Rong Chen; Jui-Cheng Kao; Che Yan; Nozomu Hiraoka; Hirofumi Ishii; Mingxing Cheng; Yu-Chieh Lo; Xin Tu; Yun-Wei Chiang; Chun-Hong Kuo; et al. (Chemical Engineering Journal, 2024)

Dual-Targeting EGCG/NO-Supplying protein assembled nanoparticles with Multi-Synergistic effects against atherosclerosis - Chi Lin; Tsai-Mu Cheng; Yun-Chun Liu; Fang-Yu Hsu; Chun-Ming Shih; Min-Lang Tsai; Chun-Che Shih; Fwu-Long Mi (Chemical Engineering Journal, 2024)

Design and performance of a micro-pulsed plasma thruster used in miniaturized satellites - Yang Ou; Jianjun Wu; Yuqiang Cheng; Yu Zhang; Bixuan Che (Advances in Space Research, 2024)

Repetitive Administration of Low-Dose Lipopolysaccharide Improves Repeated Social Defeat Stress-Induced Behavioral Abnormalities and Aberrant Immune Response - Vichuda Charoensaensuk; Wei-Lan Yeh; Bor-Ren Huang; Tsung-Che Hsu; Sheng-Yun Xie; Chao-Wei Chen; Yu-Wen Wang; Liang-Yo Yang; Cheng-Fang Tsai; Dah-Yuu Lu (Journal of Neuroimmune Pharmacology, 2024)

Estimating non-productive water losses in irrigated Platycladus orientalis plantations in semi-arid mountainous: Based on stable isotopes - Yu Zhang; Mingjun Zhang; Yuquan Qiang; Rui Lu; Cunwei Che (Science of The Total Environment, 2024)

Study on the cavity evolution and load characteristics of large projectile during high-speed water entry - Peiqi Che; Yao Shi; Hairui Zhao; Yilan Yu; Guang Pan (Ocean Engineering, 2024)

Optimizing terrestrial locomotion of undulating-fin amphibious robots: Asynchronous control and phase-difference optimization - Deliang Yu; Tianyu Che; Huibo Zhang; Chao Li; Cong Wang; Zhaotian Wang (Ocean Engineering, 2024)

Deciphering the functional importance of comammox vs. canonical ammonia oxidisers in nitrification and N2O emissions in acidic agricultural soils - Che Tan; Chang Yin; Lei Zhang; Yu Zeng; Cécile Gubry-Rangin; Hao Chen; Zixiang Gao; Hongyun Peng; Tingqiang Li; Yongchao Liang (Soil Biology and Biochemistry, 2024)

Silicate melt immiscibility as the cause of large-scale rare-metal mineralization in a peralkaline granite system: The case of the Baerzhe deposit in NE China - Hui-Min Su; Shao-Yong Jiang; Tao Jin; Yu-Ying Che; Xin-You Zhu (Lithos, 2024)

Hierarchical PVDF/ZnO/Ag/ZIF-8 nanofiber membrane used in trace-level Raman detection of H2S - Xinyu Zhang; Xin Cai; Naiqiang Yin; Yahui Che; Yang Jiao; Chao Zhang; Jing Yu; Chundong Liu (Journal of Hazardous Materials, 2024)

Cholesterol plus dietary tannins play a key role in formation of urinary stone - Yu Xi; Luyao Chen; Xiangquan Zeng; Tianyi Jiang; Shuang Yang; Xiangxin Li; Yuxia Ma; Dongdong Cao; Huilian Che; Weibo Jiang (Food Bioscience, 2024)

Chlorpyrifos-induced suppression of the antioxidative defense system leads to cytotoxicity and genotoxicity in macrophages - Yin-Che Lu; Chen-Yu Chiang; Shih-Pin Chen; Yu-Wei Hsu; Wen-Ying Chen; Chun-Jung Chen; Yu-Hsiang Kuan; Sheng-Wen Wu (Environmental Toxicology and Pharmacology, 2024)

Self-reconstructed ZIF-L/Co(OH)2 heterointerface modulates electronic structure of Ru and boosts electrocatalytic hydrogen evolution - Xinhui Yu; Yi Chen; Yuanyuan Wu; Xianyu Chu; Bo Liu; Bo Hu; Guangbo Che; Wei Jiang; Chunbo Liu (Chemical Engineering Journal, 2024)

Assessing public perceptions of the cultural ecosystem services waterfront spaces provide along the Huangpu River in Shanghai, China, in support of urban waterfront planning and design - Tian Tian; Tao Yu; Yuzhen Qian; Lingzhi Deng; Yue Che (Socio-Ecological Practice Research, 2024)

Columnar aerosol types and compositions over peninsular Southeast Asia based on long-term AERONET data - Sheng-Hsiang Wang; Hsiang-Yu Huang; Che-Hsuan Lin; Shantanu Kumar Pani; Neng-Huei Lin; Chung-Te Lee; Serm Janjai; Brent N. Holben; Somporn Chantara (Air Quality, Atmosphere & Health, 2024)
Aerosol chemical components such as black carbon (BC) and brown carbon (BrC) regulate aerosol optical properties, which in turn drive the atmospheric radiative forcing estimations due to aerosols. In this study, we used the long-term measurements from AERONET (Aerosol Robotic Network) to better understand the aerosol types and composition with respect to their seasonal and spatial variabilities in peninsular Southeast Asia (PSEA, here defined as Vietnam, Cambodia, Thailand, Laos, and Myanmar). Two methods (i.e., aerosol type cluster and aerosol component retrieval) were applied to determine the aerosol type and chemical composition during the biomass-burning (BB) season. AERONET sites in northern PSEA showed a higher AOD (aerosol optical depth) compared to that of southern PSEA. Differences in land use pattern, geographic location, and weather regime caused much of the aerosol variability over PSEA. Lower single-scattering albedo (SSA) and higher fine-mode fraction (FMF) values were observed in February and March, suggesting the predominance of BB type aerosols with finer and stronger absorbing particles during the dry season. However, we also found that the peak BB month (i.e., March) in northern PSEA may not coincide with the lowest SSA once dust particles have mixed with the other aerosols. Furthermore, we investigated two severe BB events in March of 2014 and 2015, revealing a significant BrC fraction during BB event days. On high AOD days, although the BC fraction was high, the BrC fraction remained low due to lack of aerosol aging. This study highlights the dominance of carbonaceous aerosols in the PSEA atmosphere during the BB season, while also revealing that transported dust particles and BrC aerosol aging may introduce uncertainties into the aerosol radiative forcing calculation.

Influence of low-density polyethylene addition on nitrogen transformation during sludge protein pyrolysis - Shuai Guo; Yu Wang; Jianwen Yi; Deng Zhao; Deyong Che; Hongpeng Liu; Baizhong Sun (Process Safety and Environmental Protection, 2024)

Constraining seismic anisotropy on the mantle transition zone boundaries beneath the subducting Nazca slab - Zhu Zhang; Wen-Che Yu; Hsin-Hua Huang (Physics of the Earth and Planetary Interiors, 2024)

A novel catalytic/sterilization PV-Trombe wall system: Analysis on PV electrical and air purification performance in winter - Lei Che; Niansi Li; Miaomiao Fan; Guoji Zhang; Guoyu Zhang; Bendong Yu (Building and Environment, 2024)

Key characteristics of new particle formation events occurring simultaneously in the Yangtze River Delta and northeast rural sites in China - Shuo Liu; Peng Wang; Qianli Ma; Xiaojing Shen; Hanqing Kang; Junying Sun; Quan Liu; Yangmei Zhang; Muzhen Shi; Dajiang Yu; Junting Zhong; Xinyao Hu; et al. (Atmospheric Environment, 2024)

Three-dimensional structure and transport flux of springtime smoke aerosols over the Indochina Peninsula - Yurun Liu; Ke Gui; Quanliang Chen; Liangliang Feng; Hongke Cai; Xutao Zhang; Wenrui Yao; Hengheng Zhao; Nanxuan Shang; Lei Li; Yu Zheng; Huizheng Che (Atmospheric Research, 2024)

Effects of occupational exposure to metal fume PM2.5 on lung function and biomarkers among shipyard workers: a 3-year prospective cohort study - Huan Minh Tran; Ching-Huang Lai; Wei-Liang Chen; Chung Ching Wang; Che-Wei Liang; Chi-Yu Chien; Chih-Hong Pan; Kai-Jen Chuang; Hsiao-Chi Chuang (International Archives of Occupational and Environmental Health, 2024)
Objective This study investigates the associations of α1-antitrypsin, inter-α-trypsin inhibitor heavy chain (ITIH4), and 8-isoprostane with lung function in shipyard workers exposed to occupational metal fume fine particulate matter (PM 2.5 ), which is known to be associated with adverse respiratory outcomes. Methods A 3-year follow-up study was conducted on 180 shipyard workers with 262 measurements. Personal exposure to welding fume PM 2.5 was collected for an 8-h working day. Pre-exposure, post-exposure, and delta (∆) levels of α1-antitrypsin, ITIH4, and 8-isoprostane were determined in urine using enzyme-linked immunosorbent assays. Post-exposure urinary metals were sampled at the beginning of the next working day and analyzed by inductively coupled plasma-mass spectrometry. Lung function measurements were also conducted the next working day for post-exposure. Results An IQR increase in PM 2.5 was associated with decreases of 2.157% in FEV 1 , 2.806% in PEF, 4.328% in FEF 25% , 5.047% in FEF 50% , and 7.205% in FEF 75% . An IQR increase in PM 2.5 led to increases of 42.155 µg/g in ∆α1-antitrypsin and 16.273 µg/g in ∆ITIH4. Notably, IQR increases in various urinary metals were associated with increases in specific biomarkers, such as post-urinary α1-antitrypsin and ITIH4. Moreover, increases in ∆ α1-antitrypsin and ∆ITIH4 were associated with decreases in FEV 1 /FVC by 0.008% and 0.020%, respectively, and an increase in ∆8-isoprostane resulted in a 1.538% decline in FVC. Conclusion Our study suggests that urinary α1-antitrypsin and ITIH4 could indicate early lung function decline in shipyard workers exposed to metal fume PM 2.5 , underscoring the need for better safety and health monitoring to reduce respiratory risks. Graphical abstract

Traction-based implementation of transmitting boundaries for nonlinear seismic Soil–Structure interaction analyses - Che-Yu Chang; Wen-Chia Yang; Chen-Hsiang Kuo (Soil Dynamics and Earthquake Engineering, 2024)

Metabolomics revealed more deleterious toxicity induced by the combined exposure of ammonia and nitrite on Ruditapes philippinarum compared to single exposure - Ming Cong; Zhaoshun Li; Yu Che; Yuanmei Li; Wenwen Tian; Jiasen Lv; Xiyan Sun (Marine Environmental Research, 2024)

Spatiotemporal comprehensive evaluation of water quality based on enhanced variable fuzzy set theory: A case study of a landfill in karst area - Yu Yang; Bo Li; Chaoyi Li; Pu Liu; Tao Li; Ye Luo; Lei Yang; Lulu Che; Menghua Li (Journal of Cleaner Production, 2024)

Surfeit Locus Protein 4 as a Novel Target for Therapeutic Intervention in Cerebral Ischemia–Reperfusion Injury - Wenjie Hu; Xiangyi Kong; Yu Cui; Hui Wang; Jingchen Gao; Xiyuran Wang; Shujun Chen; Xiaohua Li; Shifang Li; Fengyuan Che; Qi Wan (Molecular Neurobiology, 2024)

Soil microbial subcommunity assembly mechanisms are highly variable and intimately linked to their ecological and functional traits - Qiuping Fan; Kaifang Liu; Zelin Wang; Dong Liu; Ting Li; Haiyan Hou; Zejin Zhang; Danhong Chen; Song Zhang; Anlan Yu; Yongcui Deng; Xiaoyong Cui; et al. (Molecular Ecology, 2024)
Revealing the mechanisms underlying soil microbial community assembly is a fundamental objective in molecular ecology. However, despite increasing body of research on overall microbial community assembly mechanisms, our understanding of subcommunity assembly mechanisms for different prokaryotic and fungal taxa remains limited. Here, soils were collected from more than 100 sites across southwestern China. Based on amplicon high‐throughput sequencing and iCAMP analysis, we determined the subcommunity assembly mechanisms for various microbial taxa. The results showed that dispersal limitation and homogenous selection were the primary drivers of soil microbial community assembly in this region. However, the subcommunity assembly mechanisms of different soil microbial taxa were highly variable. For instance, the contribution of homogenous selection to Crenarchaeota subcommunity assembly was 70%, but it was only around 10% for the subcommunity assembly of Actinomycetes, Gemmatimonadetes and Planctomycetes. The assembly of subcommunities including microbial taxa with higher occurrence frequencies, average relative abundance and network degrees, as well as wider niches tended to be more influenced by homogenizing dispersal and drift, but less affected by heterogeneous selection and dispersal limitation. The subcommunity assembly mechanisms also varied substantially among different functional guilds. Notably, the subcommunity assembly of diazotrophs, nitrifiers, saprotrophs and some pathogens were predominantly controlled by homogenous selection, while that of denitrifiers and fungal pathogens were mainly affected by stochastic processes such as drift. These findings provide novel insights into understanding soil microbial diversity maintenance mechanisms, and the analysis pipeline holds significant value for future research.

Effects of coal-fired power plants on soil microbial diversity and community structures - Bowen Sun; Renbin Zhu; Yu Shi; Wanying Zhang; Zeming Zhou; Dawei Ma; Runfang Wang; Haitao Dai; Chenshuai Che (Journal of Environmental Sciences, 2024)

Agar-altered foaming bacterial cellulose with carvacrol for active food packaging applications - Anita Chandra Kusuma; Yu-Chieh Chou; Chen-Che Hsieh; Shella Permatasari Santoso; Alchris Woo Go; Hong-Ting Victor Lin; I.-Lun Hsiao; Shin-Ping Lin (Food Packaging and Shelf Life, 2024)

Columnar optical-radiative properties and components of aerosols in the Arctic summer from long-term AERONET measurements - Yuanxin Liang; Huizheng Che; Xindan Zhang; Lei Li; Ke Gui; Yu Zheng; Xutao Zhang; Hengheng Zhao; Peng Zhang; Xiaoye Zhang (Science of The Total Environment, 2024)

Detection of surface defects for maize seeds based on YOLOv5 - Yu Xia; Tianci Che; Jingwu Meng; Jinghao Hu; Gengle Qiao; Wenbo Liu; Jie Kang; Wei Tang (Journal of Stored Products Research, 2024)

The mechanism of photothermal catalytic reforming of biomass tar: An exploratory study based on density functional theory - Beibei Yan; Tianxiao Yu; Jian Li; Xiaopeng Jia; Zhiyu Li; Yuechi Che; Guanyi Chen; Juan Zhao (Fuel, 2024)

N atoms regulate heterogeneous crystal phase engineering of mesoporous magnetic FexN nanofibers to promote electromagnetic wave dissipation of magnetic composite aerogel absorbers - Wanjia Li; Wangchang Li; Zengbao Ma; Yue Kang; Ting Zou; Yu Lei; Yao Ying; Wenbo Xiang; Jing Yu; Jingwu Zheng; Liang Qiao; Juan Li; et al. (Chemical Engineering Journal, 2024)

Significant influence of nitrate on light absorption enhancement of refractory black carbon in the winter of 2022 in Beijing - Xinyao Hu; Quan Liu; Yangmei Zhang; Xiaojing Shen; Jiayuan Lu; Aoyuan Yu; Shuo Liu; Huizheng Che; Xiaoye Zhang; Junying Sun (Atmospheric Environment, 2024)

Size-resolved effective density of ambient aerosols measured by an AAC–SMPS tandem system in Beijing - Jiayuan Lu; Xiaojing Shen; Qianli Ma; Aoyuan Yu; Xinyao Hu; Yangmei Zhang; Quan Liu; Shuo Liu; Huizheng Che; Xiaoye Zhang; Junying Sun (Atmospheric Environment, 2024)

Influences of hydrodynamics on microbial community assembly and organic carbon composition of resuspended sediments in shallow marginal seas - Yangli Che; Chaoran Lin; Shen Li; Jiao Liu; Longhai Zhu; Shilei Yu; Nan Wang; Haoshuai Li; Mutai Bao; Yang Zhou; Tonghao Si; Rui Bao (Water Research, 2024)

Analysis of the spatiotemporal changes in global land cover from 2001 to 2020 - Qiaoqiao Jing; Jianjun He; Yarong Li; Xianyu Yang; Yue Peng; Hong Wang; Fei Yu; Jie Wu; Sunling Gong; Huizheng Che; Xiaoye Zhang (Science of The Total Environment, 2024)

Molecular mechanism governing RNA-binding property of mammalian TRIM71 protein - Fandi Shi; Kun Zhang; Qixuan Cheng; Shiyou Che; Shuxin Zhi; Zhenyu Yu; Fei Liu; Feifei Duan; Yangming Wang; Na Yang (Science Bulletin, 2024)

Aerosol optical and radiative properties and their environmental effects in China: A review - Huizheng Che; Xiangao Xia; Hujia Zhao; Lei Li; Ke Gui; Yu Zheng; Jingjing Song; Bing Qi; Jun Zhu; Yucong Miao; Yaqiang Wang; Zhili Wang; et al. (Earth-Science Reviews, 2024)

Exposure to phenols reduces melanogenesis in B16F10 cells and zebrafish - Chung-Yu Lin; Chang-Yi Wu; Chia C. Wang; Che-Hsin Lee (Aquatic Toxicology, 2024)

Quantitative proteomics reveals the neurotoxicity of trimethyltin chloride on mitochondria in the hippocampus of mice - Zhenzhong Liu; Li Wang; Yue Wang; Siya Wu; Caiting Peng; Yu Wang; Ming Huang; Li Che; Rongjing Sun; Xi Zhao; Zuo Du; Wenhu Liu (NeuroToxicology, 2023)

The microbial mechanisms by which long-term heavy metal contamination affects soil organic carbon levels - Zhineng Xiao; Changqun Duan; Shiyu Li; Ji Chen; Changhui Peng; Rongxiao Che; Chang'e Liu; Yin Huang; Runran Mei; Liangliang Xu; Pengfei Luo; Yadong Yu (Chemosphere, 2023)

Designing, analyzing, and experimentally verifying a uniaxial shear box for investigating the length effect of buried pipelines during soil liquefaction - Hsuan-Chih Yang; Che-Yu Chang; Kuan-Yu Chen; Hsin-Chen Chou (Transportation Geotechnics, 2023)

Analysis and classification of coffee beans using single coffee bean mass spectrometry with machine learning strategy - Jia-Jen Tsai; Che-Chia Chang; De-Yi Huang; Te-Sheng Lin; Yu-Chie Chen (Food Chemistry, 2023)

Ultrafine particles in urban settings: A combined study of volatility and effective density revealed by VT-DMA-APM - Che-An Wu; Yu-Ting Chen; Li-Hao Young; Po-Kai Chang; Li-Ti Chou; Albert Y. Chen; Ta-Chih Hsiao (Atmospheric Environment, 2023)

tDCS Regulates ASBT-3-OxoLCA-PLOD2-PTEN Signaling Pathway to Confer Neuroprotection Following Rat Cerebral Ischemia-Reperfusion Injury - Xiangyi Kong; Xujin Yao; Jinyang Ren; Jingchen Gao; Yu Cui; Jiangdong Sun; Xiangyu Xu; Wenjie Hu; Hui Wang; Huanting Li; Oleg O. Glebov; Fengyuan Che; et al. (Molecular Neurobiology, 2023)

Detection of micro-plasma-induced exosomes secretion in a fibroblast-melanoma co-culture model - Han Lee; Jiunn-Der Liao; Tak-Wah Wong; Che-Wei Wu; Bo-Yao Huang; Shun-Cheng Wu; Pei-Lin Shao; Yu-Han Wei; Ming-Hsien Cheng (Analytica Chimica Acta, 2023)

Quantifying the contribution of local drivers to observed weakening of spring dust storm frequency over northern China (1982–2017) - Ke Gui; Huizheng Che; Wenrui Yao; Yu Zheng; Lei Li; Linchang An; Hong Wang; Yaqiang Wang; Zhili Wang; Hong-Li Ren; Junying Sun; Jian Li; et al. (Science of The Total Environment, 2023)

A review of treatment technologies for acid mine drainage and sustainability assessment - Yu Yang; Bo Li; Tao Li; Pu Liu; Beibei Zhang; Lulu Che (Journal of Water Process Engineering, 2023)

Strong variation of near-surface seismic anisotropy in Taiwan and its geological implications - Hsin-Yu Lee; Yuancheng Gung; Li-Wei Chen; Wen-Shan Chen; Ying-Nien Chen; Sheng-Jyun Cai; Hui-Chu Chen; Che-Wei Liao (Earth and Planetary Science Letters, 2023)

Synchronous regulation of Schottky/p-n dual junction in Prussian blue-derived Janus heterostructures: A path to ultrafast long life potassium ion batteries - Shou-Shan Mai; Kai-Yuan Hsiao; Yi-Chun Yang; Ying-Rui Lu; Ming-Yen Lu; Yi-Yen Hsieh; Che-Bin Chang; Hsing-Yu Tuan (Chemical Engineering Journal, 2023)

Field experiments: How well can seismic monitoring assess rock mass falling? - Jui-Ming Chang; Wei-An Chao; Yu-Ting Kuo; Che-Ming Yang; Hongey Chen; Yu Wang (Engineering Geology, 2023)

Decomposition of meteorological and anthropogenic contributions to near-surface ozone trends in Northeast China (2013–2021) - Nanxuan Shang; Ke Gui; Hujia Zhao; Wenrui Yao; Hengheng Zhao; Xinglu Zhang; Xutao Zhang; Lei Li; Yu Zheng; Zhili Wang; Yaqiang Wang; Huizheng Che; et al. (Atmospheric Pollution Research, 2023)

Toxicity evaluation of silica nanoparticles for delivery applications - Yue Tan; Dawei Yu; Jiayao Feng; Huimin You; Yan Bai; Jincan He; Hua Cao; Qishi Che; Jiao Guo; Zhengquan Su (Drug Delivery and Translational Research, 2023)

Edge-based wireless imaging system for continuous monitoring of insect pests in a remote outdoor mango orchard - Dan Jeric Arcega Rustia; Wei-Che Lee; Chen-Yi Lu; Ya-Fang Wu; Pei-Yu Shih; Sheng-Kuan Chen; Jui-Yung Chung; Ta-Te Lin (Computers and Electronics in Agriculture, 2023)

Growth-promoting and low-salt adaptation responses boosted by spermidine in Strombidium parasulcatum, a marine bacteriovorous ciliate potentially applied to live feeds for marine larviculture - Hung-Yun Lin; Bo-Ying Su; Nodali Ndraha; Sheng-Fang Tsai; Kuo-Ping Chiang; Hsin-Yun Liu; Yong-Ting Kang; Wei-Yu Yeh; Che-Chia Tsao; Yi-Min Chen; Hsin-I Hsiao; Han-Jia Lin (Aquaculture, 2023)

Teleost skin microbiome: An intimate interplay between the environment and the host immunity - Liang-Chun Wang; Li-Hsuan Chen; Yu-Che Chiu; Chung-Yi Liou; Han-Chung Chen; Chia-Yun Lu; Jian-Lin Chen (Fish & Shellfish Immunology, 2023)

Air quality health index (AQHI) based on multiple air pollutants and mortality risks in Taiwan: Construction and validation - Mu-Jean Chen; Yue Leon Guo; Pinpin Lin; Hung-Che Chiang; Pau-Chung Chen; Yu-Cheng Chen (Environmental Research, 2023)

High-entropy transition metal disulfide colloid clusters: synergistic atomic scale interaction and interconnected network for ultra-stable potassium ion storage - Yan-Jie Liao; Wei-Wen Shen; Che-Bin Chang; Hsing-Yu Tuan (Chemical Engineering Journal, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

New ent -kaurene and germacrene derivatives from Mesona procumbens Hemseley and their biological activity - Jerome G. Ganzon; Chia-Ching Liaw; Yu-Chi Lin; Zhi-Hu Lin; Chang-Hung Wang; Che-Yi Chen; Kuo-Hsiang Chuang; Yao-Haur Kuo (Natural Product Research, 2023)

Effect of support condition on the mechanical behavior of ductile iron pipes buried at shallow depth within the backfill of controlled low strength material - Hsuan-Chih Yang; Che-Yu Chang; Gee-Yu Liu; Pao-Ching Chou (Transportation Geotechnics, 2023)

Multifunctional electrocatalyst based on MoCoFe LDH nanoarrays for the coupling of high efficiency Electro-Fenton and water splitting process - Fengjiang Chen; Hongchen Liu; Fan Yang; Sai Che; Neng Chen; Chong Xu; Ni Wu; Yankun Sun; Chunhui Yu; Yongfeng Li (Chemical Engineering Journal, 2023)

The city-wide full-scale interactive application of sewage surveillance programme for assisting real-time COVID-19 pandemic control – A case study in Hong Kong - Wai-yin Ng; Wai Thoe; Rong Yang; Wai-ping Cheung; Che-kong Chen; King-ho To; Kan-ming Pak; Hon-wan Leung; Wai-kwan Lai; Tsz-kin Wong; Tat-kwong Lau; Ka-wing Au; et al. (Science of The Total Environment, 2023)

Desorption performance of commercial zeolites for temperature-swing CO2 capture - Chongming Chen; Jinxing Yu; Guosheng Song; Kai Che (Journal of Environmental Chemical Engineering, 2023)

Production and analysis of metabolites from solid-state fermentation of Chenopodium formosanum (Djulis) sprouts in a bioreactor - Chen-Che Hsieh; Shu-Han Yu; Kai-Wen Cheng; Yu-Wei Liou; Cheng-Chih Hsu; Chang-Wei Hsieh; Chia-Hung Kuo; Kuan-Chen Cheng (Food Research International, 2023)

Seasonal variation of particle hygroscopicity and its impact on cloud-condensation nucleus activation in the Beijing urban area - Sinan Zhang; Xiaojing Shen; Junying Sun; Huizheng Che; Yangmei Zhang; Quan Liu; Can Xia; Xinyao Hu; Junting Zhong; Jialing Wang; Shuo Liu; Jiayuan Lu; et al. (Atmospheric Environment, 2023)

Seasonal evolution of aerosol loading and its vertical distribution in northeastern China from long-term satellite observations and model reanalysis - Hujia Zhao; Ke Gui; Yanjun Ma; Yangfeng Wang; Yaqiang Wang; Hong Wang; Yu Zheng; Lei Li; Lei Zhang; Huizheng Che; Xiaoye Zhang (Atmospheric Environment, 2023)

The degradation of subalpine meadows significantly changed the soil microbiome - Kaifang Liu; Ting Li; Xingwu Duan; Song Zhang; Meiping Chen; Haiyan Hou; Zelin Wang; Anlan Yu; Danhong Chen; Xiaoliang Zhang; Jinming Hu; Yifan Dong; et al. (Agriculture, Ecosystems & Environment, 2023)

Rab7a-mTORC1 signaling-mediated cholesterol trafficking from the lysosome to mitochondria ameliorates hepatic lipotoxicity induced by aflatoxin B1 exposure - Jin-Xian Lin; Chi-Yu Xu; Xin-Mou Wu; Lin Che; Ting-Yu Li; Su-Min Mo; Dong-Bei Guo; Zhong-Ning Lin; Yu-Chun Lin (Chemosphere, 2023)

How to accurately assess cultural ecosystem services by spatial value transfer? An answer based on the analysis of urban parks - Tian Tian; Qianqian Dong; Peng Zeng; Yaoyi Liu; Tao Yu; Yue Che (Urban Forestry & Urban Greening, 2023)

GrpE and ComD contribute to the adherence, biofilm formation, and pathogenicity of Streptococcus suis - Fei Yu; Chunliu Dong; Yuefeng Zhang; Ruixiang Che; Chunmei Xie; Yanyan Liu; Zhiyun Zhang; Lu Li; Xueying Chen; Xuehui Cai; Gang Wang; Yanhua Li (Archives of Microbiology, 2023)

Screening potential polyhydroxyalkanoate-producing bacteria from wastewater sludge - Hung‑Che Chou; Chia‑Hsin Chen; Chun‑Mei Huang; Hui‑Jun Wang; Yu-Chuan Hsiung; Chen-Hsien Liang; Chung-Mao Ou; Gia‑Luen Guo (Archives of Microbiology, 2023)

Flow measurement in open channels using imaging techniques in conjunction with a convolutional neural network - Hao-Che Ho; Yu-Wei Chiu; Ting-Yu Chen; Yen-Cheng Lin (Journal of Hydrology, 2023)

Aflatoxin B1 exposure triggers hepatic lipotoxicity via p53 and perilipin 2 interaction-mediated mitochondria-lipid droplet contacts: An in vitro and in vivo assessment - Lin Che; Jing Huang; Jin-Xian Lin; Chi-Yu Xu; Xin-Mou Wu; Ze-Bang Du; Jia-Shen Wu; Zhong-Ning Lin; Yu-Chun Lin (Journal of Hazardous Materials, 2023)

Optimized preparation of gangue waste-based geopolymer adsorbent based on improved response surface methodology for Cd(II) removal from wastewater - Chaowei Dong; Nan Zhou; Jixiong Zhang; Wanan Lai; Jianfei Xu; Junlin Chen; Runhua Yu; Yepeng Che (Environmental Research, 2023)

Design of novel double-layer coated ammonium polyphosphate and its application in flame retardant thermoplastic polyurethanes - Mei Wan; Congling Shi; Xiaodong Qian; Yueping Qin; Jingyun Jing; Honglei Che; Fei Ren; Jian Li; Bin Yu; Keqing Zhou (Chemical Engineering Journal, 2023)

Restrictions on Niobium enrichment by alteration of Niobium-rich biotite in pure water, acid, alkaline and fluoride-bearing solutions at 200 MPa and 300–600 °C - Zhao-Yu Yang; Ru-Cheng Wang; Xu-Dong Che; Daniel Harlov (Geochimica et Cosmochimica Acta, 2023)

SO2 resistance of CeO2- and Co3O4-supported activated carbon during removal of mercury from flue gas: A comparative study - Shengji Wu; Yalun Ma; Wangsheng Yu; Hui Wang; Wei Yang; Lei Che; Zhongxi Han (Fuel, 2023)

Clay nanosheets simultaneously intercalated and stabilized by PEGylated chitosan as drug delivery vehicles for cancer chemotherapy - Hsuan-Jung Huang; Shih-Yu Huang; Tzu-Hao Wang; Tzu-Yun Lin; Nan-Ching Huang; Orion Shih; U-Ser Jeng; Che-Yi Chu; Wen-Hsuan Chiang (Carbohydrate Polymers, 2023)

Bioremediation potential of cadmium by recombinant Escherichia coli surface expressing metallothionein MTT5 from Tetrahymena thermophila - Che-Wei Lu; Hsin-Cheng Ho; Chao-Ling Yao; Tsung-Yu Tseng; Chih-Ming Kao; Ssu-Ching Chen (Chemosphere, 2023)

Changes in aerosol loading before, during and after the COVID-19 pandemic outbreak in China: Effects of anthropogenic and natural aerosol - Yuanxin Liang; Ke Gui; Huizheng Che; Lei Li; Yu Zheng; Xutao Zhang; Xindan Zhang; Peng Zhang; Xiaoye Zhang (Science of The Total Environment, 2023)

Modeling study on the roles of the deposition and transport of PM2.5 in air quality changes over central-eastern China - Lei Zhang; Jianjun He; Sunling Gong; Xiaomei Guo; Tianliang Zhao; Huizheng Che; Hong Wang; Chunhong Zhou; Jingyue Mo; Ke Gui; Yu Zheng; Lei Li; et al. (Journal of Environmental Sciences, 2023)

Hydrogenation of N-ethylcarbazole with Hydrogen-Methane mixtures for hydrogen storage - Hu Liu; Jingwen Xue; Pengfei Yu; Yankang Zhang; Jinhua Wang; Defu Che (Fuel, 2023)

A low-cost eco-friendly fast drug extraction (FaDEx) technique for environmental and bio-monitoring of psychoactive drug in urban water and sports-persons’ urine samples - Swapnil Gurrani; Karthikeyan Prakasham; Jess Lim Zii Ying; Jentaie Shiea; Yi-Jia Ku; Yu-Chia Lin; Po-Chin Huang; Gangadhar Andaluri; Kung-Che Lee; Vinoth Kumar Ponnusamy (Environmental Research, 2023)

Seasonal cycles and long-term trends of arctic tropospheric aerosols based on CALIPSO lidar observations - Wenrui Yao; Ke Gui; Yu Zheng; Lei Li; Yaqiang Wang; Huizheng Che; Xiaoye Zhang (Environmental Research, 2023)

Using recoverable sulfurized magnetic biochar for active capping to remediate multiple heavy metal contaminated sediment - Che-Jung Hsu; Yung-Hua Cheng; Adrienne Chung; Ying-Pin Huang; Yu Ting; Hsing-Cheng Hsi (Environmental Pollution, 2023)

Transcranial Direct-Current Stimulation Regulates MCT1-PPA-PTEN-LONP1 Signaling to Confer Neuroprotection After Rat Cerebral Ischemia–Reperfusion Injury - Xiangyi Kong; Wenjie Hu; Yu Cui; Jingchen Gao; Xujin Yao; Jinyang Ren; Tao Lin; Jiangdong Sun; Yunyi Gao; Xiaohua Li; Hui Wang; Huanting Li; et al. (Molecular Neurobiology, 2022)
Propionic acid (PPA) is a critical metabolite involved in microbial fermentation, which functions to reduce fat production, inhibit inflammation, and reduce serum cholesterol levels. The role of PPA in the context of cerebral ischemia–reperfusion (I/R) injury has yet to be clarified. Increasing evidence indicate that transcranial direct-current stimulation (tDCS) is a safe approach that confers neuroprotection in cerebral ischemia injury. Here, we show that the levels of PPA were reduced in the ischemic brain following a rat cerebral I/R injury and in the cultured rat cortical neurons after oxygen–glucose deprivation (OGD), an in vitro model of ischemic injury. We found that the decreased levels of transporter protein monocarboxylate transporter-1 (MCT1) were responsible for the OGD-induced reduction of PPA. Supplementing PPA reduced ischemia-induced neuronal death after I/R. Moreover, our results revealed that the neuroprotective effect of PPA is mediated through downregulation of phosphatase PTEN and subsequent upregulation of Lon protease 1 (LONP1). We demonstrated that direct-current stimulation (DCS) increased MCT1 expression and PPA level in OGD-insulted neurons, while tDCS decreased the brain infarct volume in the MCAO rats via increasing the levels of MCT1 expression and PPA. This study supports a potential application of tDCS in ischemic stroke.

ceRNA network of lncRNA MIR210HG/miR-377-3p/LMX1A in malignant proliferation of glioma cells - Zhikuan Yu; Ningwei Che; Yeting He; Bo Zhang (Genes & Genomics, 2022)

Evaluating the Effect of Anisotropy on Hydraulic Stimulation in a Slate Geothermal Reservoir - Meng-Chia Weng; Po-Lin Wu; Chih-Hung Fang; Yu-Yao Fu; Yen-Che Liao; Chih-Hsi Liu (Rock Mechanics and Rock Engineering, 2022)

Assessing the impact of rockfall on the retaining structures of a mountain road: a case study in Taiwan - Che-Ming Yang; Chung-Hsun Lee; Chun-Yuan Liu; Wei-Kai Huang; Meng-Chia Weng; Yu-Yao Fu (Landslides, 2022)

Assessing phenovariant species pairs of moray eels: Hybridization, introgression, and morphology - Wen‐Chien Huang; Hong‐Ming Chen; Yung‐Che Tseng; Te‐Yu Liao (Zoologica Scripta, 2022)
Phenovariant is a pair of populations or species with distinct phenotypes but little to no genetic divergence, which may have resulted from strong assortative mating, hybridization, or incomplete lineage sorting that changes in the phenotype have exceeded the genotype. Previous studies had mainly tackled this issue on small, colourful reef fishes, but little effort has been made to the barely seen and solitary taxa like the morays (family Muraenidae). In the present study, three species pairs of sympatric morays from Taiwanese waters revealed as phenovariant in the mitochondrial cytochrome oxidase I ( COI ) were examined from the molecular and morphological perspectives, with three dissimilar scenarios discovered: (1) no hybridization was found between the morphologically most distinct Gymnothorax intesi and Gymnothorax neglectus ; (2) Gymnothorax kidako bidirectionally hybridized with Gymnothorax prionodon instead of its closely related species Gymnothorax pseudokidako ; and (3) frequently bidirectional hybridization and introgression were detected between Gymnothorax pseudothyrsoideus and Gymnothorax reevesii , a species pair that overlapped in all the morphometric and meristic characters. Nevertheless, the principal component analysis indicated that each species pair has evolved significant morphological divergence, further supporting their taxonomic validities. Our results document the natural hybridization of marine eel taxa for the first time and reveal a diverse evolutionary process among the morays.

Shallow-water hydrothermal vent system as an extreme proxy for discovery of microbiome significance in a crustacean holobiont - Ling Chiu; Min-Chen Wang; Kuang-Yu Tseng; Chih-Lin Wei; Huei-Ting Lin; Shan-Hua Yang; Yung-Che Tseng (Frontiers in Marine Science, 2022)
The shallow-water hydrothermal vent (HV) system off Kueishan Island lies at the end of the Okinawa Trough to the northeast of Taiwan. Near its submarine vent openings, aperiodic vent discharges generate a dynamic acidic (pH 5.5-8.1) and sulfidic (9-3000 μM) ecosystem. The dominant metazoan in this unique environment is the brachyuran vent crab, Xenograpsus testudinatus , which has developed robust metabolic strategies and highly adaptive acid-base regulatory mechanisms to maintain its physiological homeostasis. X. testudinatus is considered a holobiont, but the symbiotic mechanisms underlying acid and sulfur tolerance in the host-microbe system remain largely unclear. In this study, we used LoopSeq long-read sequencing of the full-length 16S rRNA gene to identify the bacterial communities present in the gills and carapace surface of X. testudinatus . The alpha diversity analysis, Venn diagram, and principal coordinate analysis (PCoA) indicated that the gills and carapace surface exhibit different bacterial constituents. Further measurements of relative abundance, coupled with functional predictions and fluorescence in situ hybridization (FISH), revealed a predominance of Sulfurovum sp. NBC37-1, a key bacterium that can perform sulfur and hydrogen oxidation to support denitrification processes. Consequently, our findings suggest that the symbiotic bacteria may play a critical role in conferring the extraordinary acid and sulfur tolerances of X. testudinatus , allowing the crustacean holobiont to thrive in its ecological niche within one of the most extreme marine habitats on Earth.

Outburst debris flow of Yusui Stream caused by a large-scale Silabaku landslide, Southern Taiwan - Che-Ming Yang; Wei-An Chao; Meng-Chia Weng; Yu-Yao Fu; Jui-Ming Chang; Wei-Kai Huang (Landslides, 2022)

Total, bioavailable and free 25-hydroxyvitamin D are associated with the prognosis of patients with non-small cell lung cancer - Si-Min Peng; Na Yu; Jun Che; Jia-Ying Xu; Guo-Chong Chen; Da-Peng Li; Yu-Song Zhang; Li-Qiang Qin (Cancer Causes & Control, 2022)

Estrogenic and anti-neutrophilic inflammatory phenanthrenes from Juncus effusus L. - Hao-Chun Hu; Yi-Hong Tsai; Yu-Che Chuang; Kuei-Hung Lai; Yu-Ming Hsu; Tsong-Long Hwang; Chih-Chan Lin; Ferenc Fülöp; Yang-Chang Wu; Szu-Yin Yu; Yu-Ting Kuo; Fang-Rong Chang (Natural Product Research, 2022)

Linear polyketides produced by co-culture of Penicillium crustosum and Penicillium fellutanum - Guihong Yu; Peng Sun; Reyilamu Aierken; Chunxiao Sun; Zhenzhen Zhang; Qian Che; Guojian Zhang; Tianjiao Zhu; Qianqun Gu; Mingyu Li; Dehai Li (Marine Life Science & Technology, 2022)

Responsiveness to contest experiences is associated with competitive ability but not aggressiveness or boldness - Yu-Ju Chen; Yu-Ting Chang; Yung-Che Tseng; Yuying Hsu (Behavioral Ecology and Sociobiology, 2022)

On-Site Investigations of Coastal Erosion and Accretion for the Northeast of Taiwan - Ting-Yu Liang; Chih-Hsin Chang; Shih-Chun Hsiao; Wei-Po Huang; Tzu-Yin Chang; Wen-Dar Guo; Che-Hsin Liu; Jui-Yi Ho; Wei-Bo Chen (Journal of Marine Science and Engineering, 2022)
Coastal erosion is a major natural hazard along the northeastern shoreline (i.e., Yilan County) of Taiwan. Analyses of the evolution of the 0 m isobath of the Yilan County coastline indicate that erosion and accretion are occurring north and south of Wushi Fishery Port, respectively, because of jetty and groin construction. Topographic and bathymetric surveys involving the measurement of 43 cross sections were conducted in 2006, 2012, 2013, and 2019. The cross-shore profile comparisons reveal that the erosion of onshore dunes is significant in the northern Jhuan River estuary. Due to the establishment of a nature reserve in the southern Lanyang River estuary, the sediments are carried northward by tidal currents, and accretion is inevitable in the northern Lanyang River estuary. The results of the bathymetric surveys also suggest that the shoreline of Yilan County tends to accrete in summer because of abundant sediment from the rivers; however, it is eroded in winter, owing to the large waves induced by the northeast monsoon. Additionally, the calculated net volume of erosion and accretion between each pair of cross sections shows that the length of coastline impacted by estuarine sediment transport is approximately 2 km long from north to south along the coastline of the Lanyang River estuary.

Downregulated Calcium-Binding Protein S100A16 and HSP27 in Placenta-Derived Multipotent Cells Induce Functional Astrocyte Differentiation - Yu-Che Cheng; Chi-Jung Huang; Wei-Chi Ku; Shu-Lin Guo; Lu-Tai Tien; Yih-Jing Lee; Chih-Cheng Chien (Stem Cell Reviews and Reports, 2022)
Little is known about genes that induce stem cells differentiation into astrocytes. We previously described that heat shock protein 27 (HSP27) downregulation is directly related to neural differentiation under chemical induction in placenta-derived multipotent stem cells (PDMCs). Using this neural differentiation cell model, we cross-compared transcriptomic and proteomic data and selected 26 candidate genes with the same expression trends in both omics analyses. Those genes were further compared with a transcriptomic database derived from Alzheimer’s disease (AD). Eighteen out of 26 candidates showed opposite expression trends between our data and the AD database. The mRNA and protein expression levels of those candidates showed downregulation of HSP27, S100 calcium-binding protein A16 (S100A16) and two other genes in our neural differentiation cell model. Silencing these four genes with various combinations showed that co-silencing HSP27 and S100A16 has stronger effects than other combinations for astrocyte differentiation. The induced astrocyte showed typical astrocytic star-shape and developed with ramified, stringy and filamentous processes as well as differentiated endfoot structures. Also, some of them connected with each other and formed continuous network. Immunofluorescence quantification of various neural markers indicated that HSP27 and S100A16 downregulation mainly drive PDMCs differentiation into astrocytes. Immunofluorescence and confocal microscopic images showed the classical star-like shape morphology and co-expression of crucial astrocyte markers in induced astrocytes, while electrophysiology and Ca 2+ influx examination further confirmed their functional characteristics. In conclusion, co-silencing of S100A16 and HSP27 without chemical induction leads to PDMCs differentiation into functional astrocytes. Graphical abstract

The Flavor and Antioxidant Activity Change Pattern of Shrimp Head Paste During Fermentation - Jing Yu; Kuan Lu; Jinyuan Sun; Wancui Xie; Lin Song; Hongxia Che (Journal of Ocean University of China, 2022)

Analytical model for uncertainty characterization of fracture intensity measurement in rock masses - Yu-Chen Lu; Yong-Ming Tien; Charng Hsein Juang; Himatul Farichah; Che-Jui Hsu; Van-Binh Bui (Bulletin of Engineering Geology and the Environment, 2022)

Associations between phthalic acid esters in house dust and home characteristics/living habits in a rural region of Taiwan - Chien-Che Hung; Tzu-Hsien Yu; Sailent Rizki Sari Simaremare; Chia-Jung Hsieh; Lih-Ming Yiin (Environmental Science and Pollution Research, 2021)

Three new species of Cylindrobasidium (Physalacriaceae, Agaricales) from East Asia - Yi-Chung Lin; Chia-Ling Wei; Chi-Yu Chen; Che-Chih Chen; Sheng-Hua Wu (Mycological Progress, 2021)

Analysis of landscape spatial pattern changes in urban fringe area: a case study of Hunhe Niaodao Area in Shenyang City - Fuer Ning; Sheng-Jung Ou; Che-Yu Hsu; Yu-Chen Chien (Landscape and Ecological Engineering, 2021)

Comparison of the Digestion and Absorption Characteristics of Docosahexaenoic Acid-Acylated Astaxanthin Monoester and Diester in Mice - Ye Li; Jie Yu; Jie Xu; Hongxia Che; Yuming Wang; Changhu Xue; Qingrong Huang; Tiantian Zhang (Journal of Ocean University of China, 2021)

Investigating the use of environmental tableware based on the theory of planned behavior - Jui-Che Tu; Yu-Yin Chen; Yi-Lin Lee; Xiao-Lin Wang (Environment, Development and Sustainability, 2021)

Detection of Vestibular Schwannoma on Triple-parametric Magnetic Resonance Images Using Convolutional Neural Networks - Tzu-Hsuan Huang; Wei-Kai Lee; Chih-Chun Wu; Cheng-Chia Lee; Chia-Feng Lu; Huai-Che Yang; Chun-Yi Lin; Wen-Yuh Chung; Po-Shan Wang; Yen-Ling Chen; Hsiu-Mei Wu; Wan-You Guo; et al. (Journal of Medical and Biological Engineering, 2021)
Purpose The first step in typical treatment of vestibular schwannoma (VS) is to localize the tumor region, which is time-consuming and subjective because it relies on repeatedly reviewing different parametric magnetic resonance (MR) images. A reliable, automatic VS detection method can streamline the process. Methods A convolutional neural network architecture, namely YOLO-v2 with a residual network as a backbone, was used to detect VS tumors from MR images. To heighten performance, T1-weighted–contrast-enhanced, T2-weighted, and T1-weighted images were combined into triple-channel images for feature learning. The triple-channel images were cropped into three sizes to serve as input images of YOLO-v2. The VS detection effectiveness levels were evaluated for two backbone residual networks that downsampled the inputs by 16 and 32. Results The results demonstrated the VS detection capability of YOLO-v2 with a residual network as a backbone model. The average precision was 0.7953 for a model with 416 × 416-pixel input images and 16 instances of downsampling, when both the thresholds of confidence score and intersection-over-union were set to 0.5. In addition, under an appropriate threshold of confidence score, a high average precision, namely 0.8171, was attained by using a model with 448 × 448-pixel input images and 16 instances of downsampling. Conclusion We demonstrated successful VS tumor detection by using a YOLO-v2 with a residual network as a backbone model on resized triple-parametric MR images. The results indicated the influence of image size, downsampling strategy, and confidence score threshold on VS tumor detection.

Schizocorticium gen. nov. (Hymenochaetales, Basidiomycota) with three new species - Sheng-Hua Wu; Chia-Ling Wei; Yu-Ping Chen; Che-Chih Chen; Siou-Zhen Chen (Mycological Progress, 2021)

Development of a region-partitioning method for debris flow susceptibility mapping - Shuang-shuang Qiao; Sheng-wu Qin; Jing-bo Sun; Wen-chao Che; Jing-yu Yao; Gang Su; Yang Chen; Uzodigwe Emmanuel Nnanwuba (Journal of Mountain Science, 2021)

Correction to: Involvement of P2Y12 receptor of stellate ganglion in diabetic cardiovascular autonomic neuropathy - Jingjing Guo; Xuan Sheng; Yu Dan; Yurong Xu; Yuanruohan Zhang; Huihong Ji; Jiayue Wang; Zixi Xu; Hongyu Che; Guodong Li; Shangdong Liang; Guilin Li (Purinergic Signalling, 2021)

Resolving misalignment interference for NGS-based clinical diagnostics - Che-yu Lee; Hai-Yun Yen; Alan W. Zhong; Hanlin Gao (Human Genetics, 2021)

Syndecan-3 contributes to the regulation of the microenvironment at the node of Ranvier following end-to‑side neurorrhaphy: sodium image analysis - Chiung-Hui Liu; Yu-Chen Kuo; Che-Yu Wang; Chao-Chun Hsu; Ying-Jui Ho; Yun-Chi Chiang; Fu-Der Mai; Wei-Jhih Lin; Wen-Chieh Liao (Histochemistry and Cell Biology, 2021)

Mapping the permafrost stability on the Tibetan Plateau for 2005–2015 - Youhua Ran; Xin Li; Guodong Cheng; Zhuotong Nan; Jinxing Che; Yu Sheng; Qingbai Wu; Huijun Jin; Dongliang Luo; Zhiguang Tang; Xiaobo Wu (Science China Earth Sciences, 2021)

TNFSF13 upregulation confers chemotherapeutic resistance via triggering autophagy initiation in triple-negative breast cancer - Hui-Yu Lin; Chia-Hao Kuei; Hsun-Hua Lee; Che-Hsuan Lin; Yen-Lin Chen; Chi-Long Chen; Yuan-Feng Lin (Journal of Molecular Medicine, 2020)

First report of leaf blight on Cattleya × hybrid caused by Neoscytalidium dimidiatum in Taiwan - Che-Wei Chang; Chi-Yu Chen; Chih-Li Wang; Wen-Hsin Chung (Journal of Plant Pathology, 2020)

A study on the effects of salinity and pH on PSII function in mulberry seedling leaves under saline–alkali mixed stress - Zhang Huihui; Li Xin; Che Yan-hui; Wang Yue; Li Ma-bo; Yang Rong-yi; Xu Nan; Sun Guang-yu (Trees, 2020)

Research Progress on Estimation of the Atmospheric Boundary Layer Height - Hongsheng Zhang; Xiaoye Zhang; Qianhui Li; Xuhui Cai; Shaojia Fan; Yu Song; Fei Hu; Huizheng Che; Jiannong Quan; Ling Kang; Tong Zhu (Journal of Meteorological Research, 2020)

Biological Protective Effects Against Vibrio Infections in Grouper Larvae Using the Strombidium sp. NTOU1, a Marine Ciliate Amenable for Scaled-Up Culture and With an Excellent Bacteriovorous Ability - Hung-Yun Lin; Wei-Yu Yeh; Sheng-Fang Tsai; Kuo-Ping Chiang; John Han-You Lin; Che-Chia Tsao; Han-Jia Lin (Frontiers in Marine Science, 2020)

GWAS reveals two novel loci for photosynthesis-related traits in soybean - Li Wang; Yuming Yang; Shuyu Zhang; Zhijun Che; Wenjie Yuan; Deyue Yu (Molecular Genetics and Genomics, 2020)

Deformation behaviors of dip slopes considering the scale effect and their geological properties - Wen-Chao Huang; Kun-Che Li; Jheng-Yu Hsieh; Meng-Chia Weng; Wen-Yi Hung (Bulletin of Engineering Geology and the Environment, 2020)

Malus niedzwetzkyana (Dieck) Langenf transcriptome comparison and phylogenetic analysis with Malus sieversii (Ledeb) Roem - Meiling Yang; Shiyou Che; Yunxiu Zhang; Wenqin Song; Guorong Yan; Weiwei Yu (Genetic Resources and Crop Evolution, 2020)

Microwave-Assisted One-Pot Synthesis of Indole-Based Fluorescent Probe for Sensitive Detection of Copper (II) - Yu-Chieh Wang; Che-Kai Wu; Jia-Lin Wang; Kwang-Ming Lee; Youn-Yuen Shu (Journal of Fluorescence, 2020)

Universal stress protein in Malus sieversii confers enhanced drought tolerance - Meiling Yang; Shiyou Che; Yunxiu Zhang; Hongbin Wang; Tao Wei; Guorong Yan; Wenqin Song; Weiwei Yu (Journal of Plant Research, 2019)

Optimization of air quality monitoring network based on a spatiotemporal-spectrum manifold analysis - Chi-Fang Wang; Ming-Che Hu; Chieh-Han Lee; Hwa-Lung Yu (Stochastic Environmental Research and Risk Assessment, 2019)

Variation in MERRA-2 aerosol optical depth over the Yangtze River Delta from 1980 to 2016 - Enwei Sun; Huizheng Che; Xiaofeng Xu; Zhenzhu Wang; Chunsong Lu; Ke Gui; Hujia Zhao; Yu Zheng; Yaqiang Wang; Hong Wang; Tianze Sun; Yuanxin Liang; et al. (Theoretical and Applied Climatology, 2019)

Development of Kriging-approximation simulated annealing optimization algorithm for parameters calibration of porous media flow model - Ming-Che Hu; Chia-Hui Shen; Shao-Yiu Hsu; Hwa-Lung Yu; Krzysztof Lamorski; Cezary Sławiński (Stochastic Environmental Research and Risk Assessment, 2019)

Detecting and attributing vegetation changes in Taihang Mountain, China - Shi Hu; Fei-yu Wang; Che-sheng Zhan; Ru-xin Zhao; Xiong-guo Mo; Liang-mei-zi Liu (Journal of Mountain Science, 2019)

The Influence of Cellulosic Polymer’s Variables on Dissolution/Solubility of Amorphous Felodipine and Crystallization Inhibition from a Supersaturated State - Nian-Qiu Shi; Ying Jin; Yong Zhang; Xiao-Xia Che; Xiao Xiao; Gui-Hua Cui; Yu-Zhou Chen; Bo Feng; Zheng-Qiang Li; Xian-Rong Qi (AAPS PharmSciTech, 2019)

Involvement of P2Y12 receptor of stellate ganglion in diabetic cardiovascular autonomic neuropathy - Jingjing Guo; Xuan Sheng; Yu Dan; Yurong Xu; Yuanruohan Zhang; Huihong Ji; Jiayue Wang; Zixi Xu; Hongyu Che; Guodong Li; Shangdong Liang; Guilin Li (Purinergic Signalling, 2018)

Energy-Based Brittleness Index and Acoustic Emission Characteristics of Anisotropic Coal Under Triaxial Stress Condition - Jun Zhang; Chi Ai; Yu-wei Li; Ming-guang Che; Rui Gao; Jia Zeng (Rock Mechanics and Rock Engineering, 2018)

A corn straw-based diet increases release of inflammatory cytokines in peripheral blood mononuclear cells of dairy cows - Yan-yi Che; Xiao-jing Xia; Bo-ping He; Yuan-yuan Gao; Wen-bo Ren; Hong-tao Liu; Jian-fang Liu; Ting-hao Huang; Wen-yu Han; Lian-cheng Lei (Journal of Zhejiang University-SCIENCE B, 2018)

Stochastic competitive analysis of hydropower and water supplies within an energy–water nexus - Ming-Che Hu; Tailin Huang; Hwa-Lung Yu; Ching-Pin Tung (Stochastic Environmental Research and Risk Assessment, 2018)

The trade network of the Belt and Road Initiative and its topological relationship to the global trade network - Zhouying Song; Shuyun Che; Yu Yang (Journal of Geographical Sciences, 2018)

Acetaminophen Poisoning May Increase Coronary Artery Disease Risk: A Nationwide Cohort Study - Yu-Ting Chung; Che-Yi Chou; Wen-Chen Tsai; Wei-Kung Chen; Cheng-Li Lin; Wei-Sheng Chung (Cardiovascular Toxicology, 2018)

Studies on the Development of Small Abalone ( Haliotis diversicolor supertexta ) Essence and its Antioxidative Properties - Yu-Wei Chang; Chun-Che Lin; Wen-Chieh Sung (Journal of Aquatic Food Product Technology, 2018)

Roaming and chaotic behaviors in collisional and photo-initiated molecular-beam reactions: a role of classical vs. quantum nonadiabatic dynamics - Toshio Kasai; Dock-Chil Che; Po-Yu Tsai; Masaaki Nakamura; Balaganesh Muthiah; King-Chuen Lin (Rendiconti Lincei. Scienze Fisiche e Naturali, 2018)

Novel TBX22 mutations in Chinese nonsyndromic cleft lip/palate families - Jiewen Dai; Chen Xu; Guomin Wang; Yun Liang; Teng Wan; Yong Zhang; Xiaofeng Xu; Lebin Yu; Zonggang Che; Qiqing Han; Dandan Wu; Yusheng Yang (Journal of Genetics, 2018)

Assessing typhoon damages to Taiwan in the recent decade: return period analysis and loss prediction - Chia-Jeng Chen; Tsung-Yu Lee; Che-Min Chang; Jun-Yi Lee (Natural Hazards, 2018)

Aerosol optical properties and radiative impacts in the Pearl River Delta region of China during the dry season - Boru Mai; Xuejiao Deng; Zhanqing Li; Jianjun Liu; Xiang’ao Xia; Huizheng Che; Xia Liu; Fei Li; Yu Zou; Maureen Cribb (Advances in Atmospheric Sciences, 2018)

Optical and radiative properties of aerosols during a severe haze episode over the North China Plain in December 2016 - Yu Zheng; Huizheng Che; Leiku Yang; Jing Chen; Yaqiang Wang; Xiangao Xia; Hujia Zhao; Hong Wang; Deying Wang; Ke Gui; Linchang An; Tianze Sun; et al. (Journal of Meteorological Research, 2017)

Neonatal Dexamethasone Treatment Exacerbates Hypoxia/Ischemia-Induced White Matter Injury - Chia -Yu Yeh; Che-Ming Yeh; Ting-Hsuan Yu; Kan-Hsun Chang; Chiung-Chun Huang; Kuei-Sen Hsu (Molecular Neurobiology, 2017)

Sex-specific nonlinear associations between serum lipids and different domains of cognitive function in middle to older age individuals - Yanhui Lu; Yu An; Huanling Yu; Fengyuan Che; Xiaona Zhang; Hongguo Rong; Yuandi Xi; Rong Xiao (Metabolic Brain Disease, 2017)

Comparison of Aerosol Optical Properties Between Two Nearby Urban Sites in Beijing, China - Jie Yu; Huizheng Che; Quanliang Chen; Hongbin Chen; Philippe Goloub; Ke Gui; Yu Zheng; Hong Wang; Yaqiang Wang; Linchang An; Tianze Sun; Xiaoye Zhang; et al. (Aerosol Science and Engineering, 2017)

The Activities of Adhesion and Biofilm Formation by Candida tropicalis Clinical Isolates Display Significant Correlation with Its Multilocus Sequence Typing - Shuan Bao Yu; Wen Ge Li; Xiao Shu Liu; Jie Che; Jin Xing Lu; Yuan Wu (Mycopathologia, 2017)

Predicted models for potential canopy rainfall interception capacity of landscape trees in Shanghai, China - Jiankang Guo; Bingqin Yu; Yuan Zhang; Shengquan Che (European Journal of Forest Research, 2017)

Three new species of Hyphodontia s.l. (Basidiomycota) with poroid or raduloid hymenophore - Che-Chih Chen; Sheng-Hua Wu; Chi-Yu Chen (Mycological Progress, 2017)

Simulating climate change impacts and potential adaptations on rice yields in the Sichuan Basin, China - Che-Chen Xu; Wen-Xiang Wu; Quan-Sheng Ge; Yang Zhou; Yu-Mei Lin; Ya-Mei Li (Mitigation and Adaptation Strategies for Global Change, 2017)

The bioconcentration ability of heavy metal research for 50 kinds of rice under the same test conditions - Wen-Juan Xie; Lei Che; Guang-Yu Zhou; Li-Na Yang; Min-Yu Hu (Environmental Monitoring and Assessment, 2016)

Characteristics of long period microtremor and validation of microtremor array measurements in inland areas of China - Ai-lan Che; Teng-yu Zhang; Shao-kon Feng (Journal of Mountain Science, 2016)

Genome-wide analysis of calcium-dependent protein kinases and their expression patterns in response to herbivore and wounding stresses in soybean - Hailun Liu; Zhijun Che; Xuanrui Zeng; Xiaoqiong Zhou; Hélder Manuel Sitoe; Hui Wang; Deyue Yu (Functional & Integrative Genomics, 2016)

Identification of single nucleotide polymorphisms in soybean associated with resistance to common cutworm (Spodoptera litura Fabricius) - Hailun Liu; Zhijun Che; Xuanrui Zeng; Guozheng Zhang; Hui Wang; Deyue Yu (Euphytica, 2016)

Serum Uric Acid Levels and Diabetic Peripheral Neuropathy in Type 2 Diabetes: a Systematic Review and Meta-analysis - Shuai Yu; Ying Chen; Xu Hou; Donghua Xu; Kui Che; Changgui Li; Shengli Yan; Yangang Wang; Bin Wang (Molecular Neurobiology, 2016)

Element distribution over the surface of fish scales and its connection to the geochemical environment of habitats: a potential biogeochemical tag - TsingHai Wang; Yan-Chen Lai; Chia-Che Chiang; Yu-Rong Cheng; Yi-Kong Hsieh; Chu-Fang Wang (Environmental Monitoring and Assessment, 2016)

G206D Mutation of Presenilin-1 Reduces Pen2 Interaction, Increases Aβ42/Aβ40 Ratio and Elevates ER Ca2+ Accumulation - Wei-Ting Chen; Yi-Fang Hsieh; Yan-Jing Huang; Che-Ching Lin; Yen-Tung Lin; Yu-Chao Liu; Cheng-Chang Lien; Irene Han-Juo Cheng (Molecular Neurobiology, 2015)

Variability in the composition and export of silica in the Huanghe River Basin - XiangBin Ran; Hong Che; JiaYe Zang; YongGui Yu; Sen Liu; LiLi Zheng (Science China Earth Sciences, 2015)

Alteration, oxygen isotope, and fluid inclusion study of the Meishan iron oxide–apatite deposit, SE China - Jinjie Yu; Linrui Che; Tiezhu Wang (Mineralium Deposita, 2015)

In Vivo Sodium MRI for Mouse Model of Ischemic Stroke at 7 T: Preliminary Results - Kun-Che Lee; Jen-Fang Yu; Yi-Shin Lee; Guo-Jen Huang; Hsiao-Lung Chan; In-Tsang Lin; Jyh-Honrg Chen (Journal of Medical and Biological Engineering, 2015)

Modeling and Analysis of the Viscoelastic Response of the Ankle Ligament Complex in Inversion Ankle Sprain - Che-Yu Lin; Yio-Wha Shau; Chung-Li Wang; Jiunn-Horng Kang (Annals of Biomedical Engineering, 2015)

Identification and quantification of Cu-chlorophyll adulteration of edible oils - Mingchih Fang; Chia-Fen Tsai; Guan-Yan Wu; Su-Hsiang Tseng; Hwei-Fang Cheng; Ching-Hao Kuo; Che-Lun Hsu; Ya-Min Kao; Daniel Yang-Chih Shih; Yu-Mei Chiang (Food Additives & Contaminants Part B-Surveillance, 2015)

Oxidative stress, apoptosis, and cell cycle arrest are induced in primary fetal alveolar type II epithelial cells exposed to fine particulate matter from cooking oil fumes - Ying Liu; Yan-Yan Chen; Ji-Yu Cao; Fang-Biao Tao; Xiao-Xia Zhu; Ci-Jiang Yao; Dao-Jun Chen; Zhen Che; Qi-Hong Zhao; Long-Ping Wen (Environmental Science and Pollution Research, 2015)

Analyses of aerosol optical properties and direct radiative forcing over urban and industrial regions in Northeast China - Huizheng Che; Hujia Zhao; Yunfei Wu; Xiangao Xia; Jun Zhu; Hong Wang; Yaqiang Wang; Junying Sun; Jie Yu; Xiaoye Zhang; Guangyu Shi (Meteorology and Atmospheric Physics, 2015)

Establishment and maintenance of a standardized glioma tissue bank: Huashan experience - Abudumijiti Aibaidula; Jun-feng Lu; Jin-song Wu; He-jian Zou; Hong Chen; Yu-qian Wang; Zhi-yong Qin; Yu Yao; Ye Gong; Xiao-ming Che; Ping Zhong; Shi-qi Li; et al. (Cell and Tissue Banking, 2015)

A measurement of summertime dry deposition of ambient air particulates and associated metallic pollutants in Central Taiwan - Guor-Cheng Fang; Hung-Che Chiang; Yu-Cheng Chen; You-Fu Xiao; Chia-Ming Wu; Yu-Chen Kuo (Environmental Geochemistry and Health, 2015)

Elucidation of anti-Vibrio factors associated with green alga Picochlorum sp. strain S1b - Jung-Che Kuo; Yu-Han Chang; Tsung-Yuan Chen; Yi-Min Chen (Journal of Applied Phycology, 2015)

The Bifunctional Liposomes Constructed by Poly(2-ethyl-oxazoline)-cholesteryl Methyl Carbonate: an Effectual Approach to Enhance Liposomal Circulation Time, pH-Sensitivity and Endosomal Escape - Huan Xu; Wei Zhang; Yan Li; Fei F. Ye; Peng P. Yin; Xiu Yu; Mei N. Hu; Yuan S. Fu; Che Wang; De J. Shang (Pharmaceutical Research, 2014)

Urinary Perchlorate Exposure and Risk in Women of Reproductive Age in a Fireworks Production Area of China - Qin Li; Yun-jiang Yu; Fei-fei Wang; Shi-wu Chen; Yan Yin; Hai-peng Lin; Fei Che; Peng Sun; Juan Qin; Jie Liu; Hong-mei Wang (Archives of Environmental Contamination and Toxicology, 2014)

An ephaptic transmission model of CA3 pyramidal cells: an investigation into electric field effects - Xile Wei; Yinhong Chen; Meili Lu; Bin Deng; Haitao Yu; Jiang Wang; Yanqiu Che; Chunxiao Han (Cognitive Neurodynamics, 2014)

Canyon-infilling and gas hydrate occurrences in the frontal fold of the offshore accretionary wedge off southern Taiwan - Che-Chuan Lin; Andrew Tien-Shun Lin; Char-Shine Liu; Chorng-Shern Horng; Guan-Yu Chen; Yunshuen Wang (Marine Geophysical Research, 2014)

AngiotensinII induces HuR shuttling by post-transcriptional regulated CyclinD1 in human mesangial cells - Yu Che; Liu Yi; Javed Akhtar; Chen Bing; Zhang Ruiyu; Wan Qiang; Wang Rong (Molecular Biology Reports, 2014)

Stability and cytotoxicity of angiotensin-I-converting enzyme inhibitory peptides derived from bovine casein - Wei Wu; Pan-pan Yu; Feng-yang Zhang; Hong-xia Che; Zhan-mei Jiang (Journal of Zhejiang University-SCIENCE B, 2014)

Aligned molecules: chirality discrimination in photodissociation and in molecular dynamics - Federico Palazzetti; Po-Yu Tsai; Andrea Lombardi; Masaaki Nakamura; Dock-Chil Che; Toshio Kasai; King-Chuen Lin; Vincenzo Aquilanti (Rendiconti Lincei. Scienze Fisiche e Naturali, 2013)

Identification and quantitative detection of Legionella spp. in various aquatic environments by real-time PCR assay - Po-Min Kao; Min-Che Tung; Bing-Mu Hsu; Yi-Chou Chiu; Cheng-Yu She; Shu-Min Shen; Yu-Li Huang; Wen-Chien Huang (Environmental Science and Pollution Research, 2013)

Catalog of Erycina pusilla miRNA and categorization of reproductive phase-related miRNAs and their target gene families - Choun-Sea Lin; Jeremy J. W. Chen; Yao-Ting Huang; Chen-Tran Hsu; Hsiang-Chia Lu; Ming-Lun Chou; Li-Chi Chen; Chia-I Ou; Der-Chih Liao; Ysuan-Yu Yeh; Song-Bing Chang; Su-Chen Shen; et al. (Plant Molecular Biology, 2013)

Differential Legionella spp. survival between intracellular and extracellular forms in thermal spring environments - Po-Min Kao; Min-Che Tung; Bing-Mu Hsu; Shih-Yung Hsu; Jen-Te Huang; Jorn-Hon Liu; Yu-Li Huang (Environmental Science and Pollution Research, 2013)

Tail loss compromises immunity in the many-lined skink, Eutropis multifasciata - Chi-Chien Kuo; Chiou-Ju Yao; Te-En Lin; Hsu-Che Liu; Yu-Cheng Hsu; Ming-Kun Hsieh; Wen-San Huang (The Science of Nature, 2013)

Ectopic Expression of Sweet Potato Cysteine Protease SPCP3 Alters Phenotypic Traits and Enhances Drought Stress Sensitivity in Transgenic Arabidopsis Plants - Hsien-Jung Chen; Yi-Jing Tsai; Che-Yu Shen; Ting-No Tsai; Guan-Jhong Huang; Yaw-Huei Lin (Journal of Plant Growth Regulation, 2013)

Moscatilin inhibits migration and metastasis of human breast cancer MDA-MB-231 cells through inhibition of Akt and Twist signaling pathway - Hui-Chen Pai; Li-Hsun Chang; Chieh-Yu Peng; Ya-Ling Chang; Chien-Chih Chen; Chien-Chang Shen; Che-Ming Teng; Shiow-Lin Pan (Journal of Molecular Medicine, 2013)

Assessment and validation of CLIGEN-simulated rainfall data for Northern Taiwan - Jen-Chen Fan; Chih-Hsiang Yang; Che-Hsin Liu; Hsiao-Yu Huang (Paddy and Water Environment, 2013)

Heat acclimation decreased oxidative DNA damage resulting from exposure to high heat in an occupational setting - Yung-Kai Huang; Che-Wei Lin; Chen-Chen Chang; Pai-Fen Chen; Chien-Jen Wang; Yu-Mei Hsueh; Hung-Che Chiang (European Journal of Applied Physiology, 2012)

Helicobacter pylori HP0876 is Dispensable for Heme–Iron Acquisition but Attenuates Bacterial Adherence to Gastric Epithelial Cells - Tao Liu; Yun Shi; Xiao-fei Liu; Ying Guo; Xu-hu Mao; Che Tan; Yuan Zhuang; Liu-sheng Peng; Jin-yu Zhang; Quan-ming Zou (Current Microbiology, 2012)

Preliminary evaluation of growth and conformation traits of local goats and Nubians upgraded by a black Boer line in Taiwan - An-Kuo Su; Shen-Suan Yang; Shui-Tsai Chen; Yu-Shin Cheng; Jan-Chi Huang; Ming-Che Wu; Jean-Paul Poivey (Tropical Animal Health and Production, 2012)

Reversine, a 2,6-disubstituted Purine, as an Anti-cancer Agent in Differentiated and Undifferentiated Thyroid Cancer Cells - Shih-Che Hua; Tien-Chun Chang; Hau-Ren Chen; Chieh-Hsiang Lu; Yi-Wen Liu; Shu-Hsin Chen; Hui-I Yu; Yi-Ping Chang; Ying-Ray Lee (Pharmaceutical Research, 2012)

Synthesis of benzopyrano[4,3-b](N-arylsulfonyl)indoles and benzopyrano[3,4-b](N-arylsulfonyl)indoles via intramolecular palladium-catalyzed aryl–aryl coupling reaction - Ling-ling Fan; Zhi-ping Che; Rui Zhang; Xiang Yu; Xiao-yan Zhi; Hui Xu (Molecular Diversity, 2012)

Induction of primitive pigment cell differentiation by visible light (helium–neon laser): a photoacceptor-specific response not replicable by UVB irradiation - Cheng-Che E. Lan; Shi-Bei Wu; Ching-Shuang Wu; Yi-Chun Shen; Tzu-Ying Chiang; Yau-Huei Wei; Hsin-Su Yu (Journal of Molecular Medicine, 2012)

PC-based artificial neural network inversion for airborne time-domain electromagnetic data - Kai-Guang Zhu; Ming-Yao Ma; Hong-Wei Che; Er-Wei Yang; Yan-Ju Ji; Sheng-Bao Yu; Jun Lin (Applied Geophysics, 2012)

Construction of a Tn5-Tagged Mutant Library of Xanthomonas oryzae pv. oryzicola as An Invaluable Resource for Functional Genomics - Hua-Song Zou; Liang Yuan; Wei Guo; Yu-Rong Li; Yi-Zhou Che; Li-Fang Zou; Gong-You Chen (Current Microbiology, 2011)

Wake-promoting agent modafinil worsened attentional performance following REM sleep deprivation in a young-adult rat model of 5-choice serial reaction time task - Yia-Ping Liu; Che-Se Tung; Yu-Lung Lin; Chia-Hsin Chuang (Psychopharmacology, 2011)

Porcine lactoferrin as feedstuff additive elevates avian immunity and potentiates vaccination - Che-Ming Hung; Shinn-Chih Wu; Chih-Ching Yen; Ming-Fong Lin; Yi-Wen Lai; Yu-Tang Tung; Hsiao-Ling Chen; Chuan-Mu Chen (BioMetals, 2010)

On the intensity and type transition of land use at the basin scale using RS/GIS: a case study of the Hanjiang River Basin - Guangming Yu; Qun Zeng; Shan Yang; Limei Hu; Xiaowei Lin; Yi Che; Yuge Zheng (Environmental Monitoring and Assessment, 2010)

Chronic treatment with monoamine oxidase-B inhibitors decreases cocaine reward in mice - Ming-Che Ho; Chianfang G. Cherng; Yen-Ping N. Tsai; Chih-Yuan Chiang; Jia-Ying Chuang; Shu-Fang Kao; Lung Yu (Psychopharmacology, 2009)

A vitronectin M381T polymorphism increases risk of hemangioblastoma in patients with VHL gene defect - Jing-Shan Huang; Chih-Ming Lin; Yu-Che Cheng; Kun-Long Hung; Chih-Cheng Chien; Shao-Kuan Chen; Chih-Ju Chang; Chan-Wei Chen; Chi-Jung Huang (Journal of Molecular Medicine, 2009)

Baicalein attenuates intimal hyperplasia after rat carotid balloon injury through arresting cell-cycle progression and inhibiting ERK, Akt, and NF-κB activity in vascular smooth-muscle cells - Chieh-Yu Peng; Shiow-Lin Pan; Ying-Wen Huang; Jih-Hwa Guh; Ya-Ling Chang; Che-Ming Teng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

PM2.5 and Associated Polycyclic Aromatic Hydrocarbon and Mutagenicity Emissions from Motorcycles - Hsi-Hsien Yang; Shu-An Lee; Dennis P. H. Hsieh; Mu-Rong Chao; Che-Yu Tung (Bulletin of Environmental Contamination and Toxicology, 2008)

A study of NO trafficking from dinitrosyl–iron complexes to the recombinant E. coli transcriptional factor SoxR - Feng-Chun Lo; Chang-Li Chen; Chien-Ming Lee; Ming-Che Tsai; Tsai-Te Lu; Wen-Feng Liaw; Steve S.-F. Yu (JBIC Journal of Biological Inorganic Chemistry, 2008)

Silver nanoparticles: partial oxidation and antibacterial activities - Chun-Nam Lok; Chi-Ming Ho; Rong Chen; Qing-Yu He; Wing-Yiu Yu; Hongzhe Sun; Paul Kwong-Hang Tam; Jen-Fu Chiu; Chi-Ming Che (JBIC Journal of Biological Inorganic Chemistry, 2007)

Postnatal expression and denervation induced up-regulation of aquaporin-5 protein in rat sweat gland - Lei Ma; Yuan-Gui Huang; Hua He; Yan-Chun Deng; Hai-Feng Zhang; Hong-Lei Che; Ji-Yu Tian; Gang Zhao (Cell and Tissue Research, 2007)

Influence of glaciation on divergence patterns of the endemic minnow, Zacco pachycephalus , in Taiwan - Hurng‐Yi Wang; Mung‐Pei Tsai; Ming‐Jenn Yu; Sin‐Che Lee (Molecular Ecology, 1999)
The genetic subdivision of the endemic minnow, Zacco pachycephalus , in 12 rivers of Taiwan was studied by allozyme electrophoresis. Among 26 loci surveyed, six were significantly differentiated among sites. Allozyme genotype frequencies within samples accord with Hardy–Weinberg expectations. A highly divergent genetic structure among sites ( F ST = 0.497) with low genetic variability within samples ( H = 0.006–0.062, mean = 0.03) suggests that local populations originated from a small number of founders. upgma and Fitch trees derived from Nei’s genetic distance and hierarchical analysis of F ST values reveal that samples of Z. pachycephalus can be divided into northern, middle, and southern subgroups and that most genetic variation (87%) is distributed among rather than within groups. It is proposed that there were two isolated refugia during the most recent glacial period, and that populations of the southern group (Group I) originated from a southern refugium in Taiwan below the boundary of the Kaoping River, and other groups (Group II), including northern and middle subgroups, originated from a refugium located on the extinct landbridge between Taiwan and mainland China. The postglacial division between northern and middle subgroups may be due to hydrological differences between these two regions.